Adhesive composition, adhesive layer, adhesive sheet, optical member with adhesive layer, image display device, and touch panel

By developing an adhesive composition that meets the specific water absorption rate and water absorption time, the problems of unstable adhesive force and low productivity of the adhesive layer in severe environments are solved, and high reliability and excellent adhesive properties are achieved.

CN119144252APending Publication Date: 2024-12-17NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410767522.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-16
Filing Date
2024-06-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

When used in harsh environments such as high temperature, high humidity and sunlight, the adhesive force is unstable and the productivity is low, making it difficult to meet the reliability requirements of vehicle-based displays.

Method used

A binder composition is developed with a water absorption rate of X90≤1.5% at 23°C, 90% RH, a water absorption rate of X25≤1.5% at 25% RH, and until the water absorption reaches between X75 and X90 The time T90≥16 minutes until the half value is T90, and these indicators ensure excellent adhesion stability and productivity.

Benefits of technology

High reliability of stable adhesive force during environmental changes is achieved, the adhesive force changes caused by the storage environment are reduced, productivity is improved, and excellent adhesive performance is maintained in various environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004892994950000251
    Figure BDA0004892994950000251
  • Figure BDA0004892994950000311
    Figure BDA0004892994950000311
  • Figure BDA0004892994950000351
    Figure BDA0004892994950000351
Patent Text Reader

Abstract

The invention provides an adhesive composition, an adhesive layer, an adhesive sheet, an optical member with an adhesive layer, an image display device, and a touch panel, and the adhesive composition is used for forming an adhesive layer used for pasting the optical member of the image display device. The adhesive composition is capable of forming an adhesive layer having high reliability in which the adhesive force does not easily change with respect to an environmental change, having little change in adhesive force due to a storage environment immediately after film formation, and having excellent productivity. The adhesive composition is used for forming an adhesive layer used for pasting an optical member of an image display device, and when the water absorption rate of the adhesive layer stored for 360 minutes under the conditions of 23 DEG C and 90% RH is set as X90 (%), the formula (1) is satisfied. X90 < = 1.5%... (1)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an adhesive composition, an adhesive layer, an adhesive sheet, an optical member with an adhesive layer, an image display device, and a touch panel. Background Art

[0002] In recent years, image display devices such as liquid crystal displays (LCDs) and organic electroluminescent displays (OLEDs), and touch panels in which touch sensors are assembled in these image display devices are widely used in various fields. Such image display devices and touch panels have a structure in which various optical components such as a polarizing film, a phase difference film, an optical compensation film, a touch sensor film, and a cover film are stacked on the image display panel. Adhesive sheets having an adhesive layer are used for bonding these optical components. For example, transparent adhesive sheets are used for bonding various optical components in image display devices (for example, refer to Patent Documents 1 to 3).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2003-238915

[0006] Patent Document 2: Japanese Patent Application Publication No. 2003-342542

[0007] Patent Document 3: Japanese Patent Application Publication No. 2004-231723 Summary of the invention

[0008] Problems to be solved by the invention

[0009] The above-mentioned image display devices and touch panels are also widely used in vehicle-mounted displays such as car navigation devices. Vehicle-mounted displays are often exposed to harsh environments such as high temperature, high humidity, and sunlight for a long time, and high reliability is required. In particular, with the popularization of electric vehicles (EV), the screens will become larger and curved in the future, and the required reliability will increase year by year, requiring highly reliable adhesives whose properties such as adhesion are stable even when the environment changes. In addition, in the case where the adhesion force changes significantly due to the storage environment just after the adhesive layer is formed into a film, there is also the following problem: it is necessary to leave it until the adhesion force is stable, which reduces productivity.

[0010] Therefore, the object of the present invention is to provide an adhesive composition, which is an adhesive composition for forming an adhesive layer used for pasting an optical component of an image display device, wherein the adhesive composition can form an adhesive layer having high reliability, stable adhesive force even if the environment changes, small change in adhesive force caused by the storage environment just after filming, and excellent productivity. In addition, another object of the present invention is to provide an adhesive layer, which has high reliability, stable adhesive force even if the environment changes, small change in adhesive force caused by the storage environment just after filming, and excellent productivity. In addition, another object of the present invention is to provide an adhesive sheet having an adhesive layer, which has high reliability, stable adhesive force even if the environment changes, small change in adhesive force caused by the storage environment just after filming, and excellent productivity. In addition, another object of the present invention is to provide an optical component with an adhesive layer, which has high reliability, stable adhesive force even if the environment changes, small change in adhesive force caused by the storage environment just after filming, and excellent productivity. In addition, another object of the present invention is to provide an image display device and a touch panel having the above-mentioned optical component with an adhesive layer, high reliability, excellent durability, and high performance even if the environment changes.

[0011] Means used to solve problems

[0012] A first aspect of the present invention provides a pressure-sensitive adhesive composition for forming a pressure-sensitive adhesive layer used for bonding optical members of an image display device. In this specification, the pressure-sensitive adhesive composition of the first aspect of the present invention may be referred to as "the pressure-sensitive adhesive composition of the present invention."

[0013] The adhesive composition of the present invention is used in image display devices such as liquid crystal displays (LCDs) and organic electroluminescent displays (OLEDs), and touch panels in which touch sensors are assembled in these image display devices, to adhere optical components such as polarizing films, phase difference films, optical compensation films, touch sensor films, and cover films to image display panels, or to form an adhesive layer used for adhering these optical components to each other.

[0014] The adhesive composition of the present invention is particularly suitable for use in vehicle-mounted image display devices and touch panels. Vehicle-mounted displays are often exposed to harsh environments such as high temperature, high humidity, and sunlight for a long time, and require high reliability that properties such as adhesive strength do not easily change even if the environment changes. In addition, there is also the following problem: when the adhesive strength changes significantly due to the storage environment just after the adhesive layer is formed into a film, it is necessary to leave it until the adhesive strength is stabilized, which reduces productivity.

[0015] The adhesive composition of the present invention satisfies the following formula (1) when the water absorption rate of the adhesive layer when stored under the conditions of 23° C. and 90% RH for 360 minutes is defined as X90(%).

[0016] X90≤1.5% …… (1)

[0017] The water absorption X90 is the ratio of water absorbed by the adhesive layer in a high humidity environment such as 90% RH. The water absorption X90 satisfies the above formula (1), that is, the water absorption X90 is less than 1.5%. When the water absorption X90 is high, the swelling and shrinkage of the adhesive layer caused by environmental changes become larger, and the elastic modulus changes. In addition, sometimes the water contained in the adhesive interacts with the polar groups on the surface of the adhesive, hindering the interaction between the polar groups on the surface of the adhesive and the polar groups on the surface of the adherend, affecting the adhesive force. The structure in which the water absorption X90 satisfies the above formula (1) is preferred from the perspective of obtaining a highly reliable adhesive layer whose adhesive force is not easily changed with respect to environmental changes such as temperature and humidity. In addition, it is also preferred from the perspective of obtaining an adhesive layer with small changes in adhesive force caused by the storage environment just after film formation and excellent productivity.

[0018] The pressure-sensitive adhesive composition of the present invention preferably satisfies the following formula (2), where the water absorption rate of the pressure-sensitive adhesive layer when stored under conditions of 23° C. and 25% RH for 240 minutes is defined as X25 (%).

[0019] X90-X25≤1.5%……(2)

[0020] The water absorption rate X25 is the ratio of water absorbed by the adhesive layer in a dry environment such as 25% RH. As described above, the difference between the water absorption rate X90 and the water absorption rate X25 (X90-X25) preferably satisfies the above formula (2), that is, it is preferably 1.5% or less. When the difference between X25 and X90 is large, the change in the amount of water contained in the adhesive layer caused by the environment sometimes becomes larger, the influence on the adhesive force also becomes larger, and the reliability is reduced. The structure in which the difference X90-X25 satisfies the above formula (2) is preferred from the perspective of obtaining an adhesive layer with high reliability and which is not easily changed in adhesion with environmental changes such as temperature and humidity, and which can be used in various environments. In addition, it is also preferred from the perspective of obtaining an adhesive layer with small changes in adhesion caused by the storage environment just after film formation and excellent productivity.

[0021] The adhesive composition of the present invention preferably satisfies the following formula (3) when the time until the water absorption reaches the half value of the water absorption between X75 (%) and X90 (%) is defined as T90 (minutes).

[0022] T90≥16 minutes……(3)

[0023] The X75 is the water absorption rate when the adhesive layer is stored at 23° C. and 75% RH for 360 minutes, and the X90 is the water absorption rate when the adhesive layer is stored at 23° C. and 90% RH for 360 minutes.

[0024] The T90 is the time until the water absorption reaches the half value of the water absorption between X75 (%) and X90 (%), the X75 is the water absorption when the adhesive layer is stored at 23°C and 75% RH for 360 minutes, and the X90 is the water absorption when the adhesive layer is stored at 23°C and 90% RH for 360 minutes. Until the water absorption reaches the half value, the moisture content changes (increases) most dramatically. Therefore, the longer the T90 is, the slower the rate of water absorption is, and even if the environment changes, a sharp change in adhesion can be prevented. The configuration in which the T90 satisfies the above formula (3), that is, the T90 is more than 16 minutes, is preferred from the perspective of obtaining an adhesive layer that can prevent a sharp change in adhesion caused by environmental changes and has high reliability. In addition, it is also preferred from the perspective of obtaining an adhesive layer with a small change in adhesion caused by the storage environment just after film formation and excellent productivity.

[0025] The adhesive composition of the present invention preferably satisfies the following formula (4) when T25 (minutes) is the time until the water absorption reaches half the value of the water absorption between the absolute dry state and X25 (%).

[0026] T90 / T25≥1.0 …… (4)

[0027] The X25 is the water absorption rate when the pressure-sensitive adhesive layer is stored under the conditions of 23° C. and 25% RH for 240 minutes.

[0028] The T90 / T25 preferably satisfies the above formula (4), that is, the T90 / T25 is preferably greater than 1.0. If the higher the humidity, the slower the rate at which the adhesive layer absorbs moisture, it is possible to prevent a sharp change in the adhesive force caused by environmental changes, and it can be used in various environments. The structure in which the T90 / T25 satisfies the above formula (4) is preferred from the perspective of obtaining an adhesive layer that can prevent a sharp change in the adhesive force caused by environmental changes, has high reliability, and can be used in various environments. In addition, it is also preferred from the perspective of obtaining an adhesive layer with little change in the adhesive force caused by the storage environment just after film formation and excellent productivity.

[0029] The second aspect of the present invention provides an adhesive layer formed from the adhesive composition of the present invention. In this specification, the adhesive layer of the second aspect of the present invention is sometimes referred to as "the adhesive layer of the present invention". The adhesive layer of the present invention is formed from the adhesive composition of the present invention, and is therefore preferred from the viewpoints of high reliability, stable adhesive force even when the environment changes, small changes in adhesive force caused by the storage environment just after film formation, and excellent productivity.

[0030] The third aspect of the present invention provides an adhesive sheet having an adhesive layer of the present invention. In this specification, the adhesive sheet of the third aspect of the present invention is sometimes referred to as "the adhesive sheet of the present invention". The adhesive sheet of the present invention has the adhesive layer of the present invention, and is therefore preferred from the viewpoints of high reliability, stable adhesive force even when the environment changes, small changes in adhesive force caused by the storage environment just after the adhesive layer is formed into a film, and excellent productivity.

[0031] The fourth aspect of the present invention provides an optical component with an adhesive layer, wherein the adhesive sheet of the present invention is attached to at least one surface of the optical component. In this specification, the optical component with an adhesive layer of the fourth aspect of the present invention is sometimes referred to as "the optical component with an adhesive layer of the present invention". The optical component with an adhesive layer of the present invention has the adhesive layer of the present invention, and therefore is preferred from the viewpoint of high reliability that the adhesive force is stable even if the environment changes.

[0032] The fifth aspect of the present invention provides an image display device having the optical member with a pressure-sensitive adhesive layer of the present invention. In this specification, the image display device of the fifth aspect of the present invention may be referred to as "the image display device of the present invention." The image display device of the present invention may be a touch panel.

[0033] In the image display device and touch panel of the present invention, optical members are bonded together using the pressure-sensitive adhesive layer of the present invention, and therefore, the pressure-sensitive adhesive layer is preferably used from the viewpoint of high reliability and excellent durability, since the pressure-sensitive adhesive force is stable even when the environment changes.

[0034] Effects of the Invention

[0035] The adhesive composition of the present invention can form an adhesive layer with high reliability and stable adhesive force even when the environment changes, small change in adhesive force caused by the storage environment just after film formation, and excellent productivity. Therefore, by bonding optical components using an adhesive sheet having an adhesive layer formed from the adhesive composition of the present invention, a high-performance image display device and touch panel with high reliability and excellent durability can be effectively manufactured even when the environment changes and the adhesive force is stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1It is a schematic diagram showing a specific example of a preferred embodiment of the pressure-sensitive adhesive sheet of the present invention.

[0037] Figure 2 It is a schematic diagram which shows the specific example of the preferable aspect of the optical member with a pressure-sensitive adhesive layer of this invention.

[0038] Figure 3 It is a schematic diagram showing a specific example of a preferred embodiment of the image display device of the present invention.

[0039] Figure 4 It is a schematic diagram showing a specific example of a preferred embodiment of the touch panel of the present invention.

[0040] Figure 5 The figures show the results of adhesive force measurement in the examples and comparative examples of the present application. (a) is a figure showing the results of Example 1, (b) is a figure showing the results of Example 2, (c) is a figure showing the results of Example 3, and (d) is a figure showing the results of Comparative Example 1.

[0041] Description of symbols

[0042] 1 Adhesive sheet

[0043] 10 Adhesive layer

[0044] 11, 12 Release liner

[0045] 2A Optical member with adhesive layer

[0046] 2B Touch sensor film with adhesive layer

[0047] 20 Adhesive layer

[0048] 21 Optical components

[0049] 22 Release liner

[0050] 23 Touch sensor film

[0051] 24 Metal wiring

[0052] 3 Image display device

[0053] 30, 31, 32 adhesive layer

[0054] 33 Image display panel

[0055] 34, 35 Polarizing film

[0056] 36 transparent substrate

[0057] 4 Touch Panel

[0058] 40, 41, 42 adhesive layer

[0059] 43 Image display panel

[0060] 44 Touch sensor film

[0061] 45 Polarizing film

[0062] 46 transparent substrate

[0063] 47 Metal wiring DETAILED DESCRIPTION

[0064] [1. Adhesive composition and adhesive layer]

[0065] The adhesive composition of the present invention is an adhesive composition for forming an adhesive layer used for bonding optical members of an image display device, wherein:

[0066] When the water absorption rate of the pressure-sensitive adhesive layer when stored under the conditions of 23° C. and 90% RH for 360 minutes is defined as X90 (%), the following formula (1) is satisfied.

[0067] X90≤1.5% …… (1)

[0068] The adhesive composition of the present invention is used in image display devices such as liquid crystal displays (LCDs) and organic electroluminescent displays (OLEDs), and touch panels in which touch sensors are assembled in these image display devices, to adhere optical components such as polarizing films, phase difference films, optical compensation films, touch sensor films, and cover films to image display panels, or to form an adhesive layer used for adhering these optical components to each other.

[0069] In addition, in this specification, when referring to an "image display device", unless otherwise specified, a "touch panel" is also included.

[0070] The adhesive composition of the present invention is particularly suitable for use in vehicle-mounted image display devices and touch panels. Vehicle-mounted displays are often exposed to harsh environments such as high temperature, high humidity, and sunlight for a long time, and require high reliability that properties such as adhesive strength do not easily change even if the environment changes. In addition, there is also the following problem: when the adhesive strength changes significantly due to the storage environment just after the adhesive layer is formed into a film, it is necessary to leave it until the adhesive strength is stabilized, which reduces productivity.

[0071] It is believed that the reason why the adhesive force changes according to the environment is that due to the change in the amount of water absorbed by the adhesive layer, the swelling and contraction of the adhesive layer become larger, the elastic modulus changes, and in addition, the water contained in the adhesive interacts with the polar groups on the surface of the adhesive, hindering the interaction between the polar groups on the surface of the adhesive and the polar groups on the surface of the adherend, affecting the adhesive force. Therefore, it is believed that even if the environment changes and the change in the amount of water absorbed by the adhesive layer is small, the influence on the adhesive force becomes small, and a highly reliable adhesive layer can be obtained.

[0072] The water absorption X90 is the ratio of water absorbed by the adhesive layer of the present invention in a high humidity environment such as 90% RH. When the water absorption X90 is high, the swelling and shrinkage of the adhesive layer caused by environmental changes become larger. In addition, sometimes the water contained in the adhesive hinders the interaction between the polar groups on the surface of the adhesive and the polar groups on the surface of the adherend, affecting the adhesive force. The water absorption X90 satisfies the above formula (1), that is, the water absorption X90 is 1.5% or less. Such a structure is preferred from the perspective of obtaining a highly reliable adhesive layer whose adhesive force is not easily changed with respect to environmental changes such as temperature and humidity. In addition, it is also preferred from the perspective of obtaining an adhesive layer with a small change in adhesive force caused by the storage environment just after film formation and excellent productivity.

[0073] From the perspective of obtaining an adhesive layer having high reliability that the adhesive force is not easily changed with respect to environmental changes, small changes in the adhesive force caused by the storage environment immediately after film formation, and excellent productivity, the water absorption X90 is preferably 1.4% or less, more preferably 1.3% or less, further preferably 1.2% or less, and can be 1.1% or less. The lower limit of the water absorption X90 is not particularly limited, and the lower the better, but it can be 0.5% or more.

[0074] The adhesive composition of the present invention preferably satisfies the following formula (2), where the water absorption of the adhesive layer of the present invention when stored under the conditions of 23° C. and 25% RH for 240 minutes is defined as X25 (%).

[0075] X90-X25≤1.5%……(2)

[0076] The water absorption rate X25 is the ratio of water absorbed by the adhesive layer in a dry environment such as 25% RH. When the difference between X25 and the above X90 is large, the amount of water contained in the adhesive layer may change greatly depending on the environment, and the influence on the adhesive force may also increase, thereby reducing reliability. A configuration in which the difference between the above water absorption rate X90 and the water absorption rate X25 (X90-X25) satisfies the above formula (2), i.e., is 1.5% or less is preferred from the perspective of obtaining an adhesive layer with high reliability and which is not easily changed in adhesive force due to environmental changes such as temperature and humidity, and which can be used in various environments. In addition, it is also preferred from the perspective of obtaining an adhesive layer with small changes in adhesive force caused by the storage environment just after film formation and excellent productivity.

[0077] From the perspective of obtaining an adhesive layer having high reliability that does not easily change the adhesive force against environmental changes, being able to be used in various environments, having little change in the adhesive force caused by the storage environment immediately after film formation, and having excellent productivity, the above difference X90-X25 is preferably 1.4% or less, more preferably 1.3% or less, further preferably 1.2% or less, and may be 1.1% or less or 1.0% or less. The lower limit of the above difference X90-X25 is not particularly limited, and the lower the better, but may be 0.5% or more.

[0078] The adhesive composition of the present invention preferably satisfies the following formula (3) when the time until the water absorption reaches the half value of the water absorption between X75 (%) and X90 (%) is defined as T90 (minutes).

[0079] T90≥16 minutes……(3)

[0080] The X75 is the water absorption rate when the adhesive layer is stored at 23° C. and 75% RH for 360 minutes, and the X90 is the water absorption rate when the adhesive layer is stored at 23° C. and 90% RH for 360 minutes.

[0081] Here, the "half value" refers to the half value of the water absorption rate from X75 to X90, that is, the water absorption rate (%) expressed by the formula: (X90-X75) / 2. In addition, the "time until the half value is reached" refers to the time from the time point of starting storage under the conditions of 23°C and 90%RH until the above-mentioned "half value" is reached. The same applies to the "half values" in T25, T50, and T75 described later.

[0082] The T90 is the time until the water absorption reaches the half value of the water absorption between X75 (%) and X90 (%), the X75 is the water absorption when the adhesive layer is stored at 23°C and 75% RH for 360 minutes, and the X90 is the water absorption when the adhesive layer is stored at 23°C and 90% RH for 360 minutes. Until the half value is reached, the moisture content changes (increases) most dramatically. Therefore, the longer the T90 is, the slower the rate of water absorption is, and even if the environment changes, a sharp change in adhesion can be prevented. The configuration in which the T90 satisfies the above formula (3), that is, the T90 is more than 16 minutes, is preferred from the perspective of obtaining an adhesive layer that can prevent a sharp change in adhesion caused by environmental changes and has high reliability. In addition, it is also preferred from the perspective of obtaining an adhesive layer with a small change in adhesion caused by the storage environment just after film formation and excellent productivity.

[0083] From the perspective of obtaining an adhesive layer that can prevent a sharp change in adhesive force caused by environmental changes, has high reliability, has little change in adhesive force caused by the storage environment immediately after film formation, and has excellent productivity, the T90 is preferably 17 minutes or more, more preferably 18 minutes or more, further preferably 19 minutes or more, and may be 20 minutes or more. The upper limit of the T90 is not particularly limited, and the longer the better, but may be 60 minutes or less.

[0084] The adhesive composition of the present invention preferably satisfies the following formula (4) when T25 (minutes) is the time until the water absorption reaches half the value of the water absorption between the absolute dry state and X25 (%).

[0085] T90 / T25≥1.0 …… (4)

[0086] The X25 is the water absorption rate when the pressure-sensitive adhesive layer is stored under the conditions of 23° C. and 25% RH for 240 minutes.

[0087] Here, the above-mentioned "absolute dry state" refers to a state in which the weight of the adhesive layer does not further decrease even if it is left to stand under dry conditions. In this specification, the weight of the adhesive layer after being stored at 150°C, 0% RH for 60 minutes and then stored at 23°C, 0% RH for 240 minutes does not substantially decrease even if it is further stored, and is therefore referred to as the "absolute dry state".

[0088] If the adhesive layer absorbs water more slowly under high humidity conditions, it is possible to prevent a sharp change in adhesive force caused by environmental changes, and the adhesive layer can be used in various environments. The configuration in which the T90 / T25 satisfies the above formula (4), i.e., the T90 / T25 is 1.0 or more, is preferred from the perspective of obtaining an adhesive layer that can prevent a sharp change in adhesive force caused by environmental changes, has high reliability, and can be used in various environments. In addition, it is also preferred from the perspective of obtaining an adhesive layer that has a small change in adhesive force caused by the storage environment just after film formation and has excellent productivity.

[0089] From the perspective of obtaining an adhesive layer that can prevent a sharp change in adhesive force caused by environmental changes, has high reliability, can be used in various environments, has little change in adhesive force caused by the storage environment just after film formation, and has excellent productivity, the above T90 / T25 is preferably 1.1 or more, more preferably 1.2 or more, further preferably 1.3 or more, and can be 1.4 or more. The upper limit of the above T90 / T25 is not particularly limited, and the higher the better, but it can be 2.0 or less.

[0090] From the perspective of obtaining an adhesive layer having high reliability that the adhesive force is not easily changed with respect to environmental changes, small changes in the adhesive force caused by the storage environment immediately after film formation, and excellent productivity, the water absorption rate X25 is preferably 0.3% or less, more preferably 0.25% or less, further preferably 0.2% or less, and can be 0.15% or less. The lower limit of the water absorption rate X25 is not particularly limited, and the lower the better, but it can be 0.01% or more.

[0091] When the water absorption of the adhesive layer of the present invention when stored for 240 minutes under the conditions of 23°C and 50%RH is set to X50 (%), from the perspective of obtaining an adhesive layer having high reliability that the adhesive force is not easily changed with respect to environmental changes, small changes in the adhesive force caused by the storage environment just after film formation, and excellent productivity, the water absorption X50 is preferably 0.8% or less, more preferably 0.7% or less, further preferably 0.6% or less, and can be 0.5% or less. The lower limit of the water absorption X50 is not particularly limited, and the lower the better, but it can be 0.1% or more.

[0092] When the water absorption of the adhesive layer of the present invention when stored for 360 minutes under the conditions of 23°C and 75%RH is set to X75 (%), from the perspective of obtaining an adhesive layer having high reliability that the adhesive force is not easily changed relative to environmental changes, small changes in the adhesive force caused by the storage environment just after film formation, and excellent productivity, the water absorption X75 is preferably 1.2% or less, more preferably 1.1% or less, further preferably 1.0% or less, and can be 0.9% or less or 0.8% or less. The lower limit of the water absorption X75 is not particularly limited, and the lower the better, but it can be 0.3% or more.

[0093] From the perspective of obtaining an adhesive layer that can prevent a sharp change in adhesive force caused by environmental changes, has high reliability, has little change in adhesive force caused by the storage environment just after film formation, and has excellent productivity, the above T25 is preferably 16 minutes or more, more preferably 17 minutes or more, further preferably 18 minutes or more, and can be 19 minutes or more or 20 minutes or more. The upper limit of the above T25 is not particularly limited, and the longer the better, but it can be 60 minutes or less.

[0094] When the time until the water absorption reaches the half value of the water absorption between X25 (%) and X50 (%) is set as T50 (minutes), the X25 is the water absorption when the adhesive layer is stored at 23°C and 25% RH for 240 minutes, and the X50 is the water absorption when the adhesive layer is stored at 23°C and 50% RH for 240 minutes. From the perspective of obtaining an adhesive layer that can prevent a sharp change in adhesion caused by environmental changes, has high reliability, has a small change in adhesion caused by the storage environment just after film formation, and has excellent productivity, the T50 is preferably 16 minutes or more, more preferably 17 minutes or more, and further preferably 18 minutes or more, and can be 19 minutes or more or 20 minutes or more. The upper limit of the above T50 is not particularly limited, and the longer the better, but it can be 60 minutes or less.

[0095] When the time until the water absorption reaches the half value of the water absorption between X50 (%) and X75 (%) is set as T75 (minutes), the X50 is the water absorption when the adhesive layer is stored at 23°C and 50% RH for 240 minutes, and the X75 is the water absorption when the adhesive layer is stored at 23°C and 75% RH for 360 minutes. From the perspective of obtaining an adhesive layer that can prevent a sharp change in adhesion caused by environmental changes, has high reliability, has a small change in adhesion caused by the storage environment just after film formation, and has excellent productivity, the T75 is preferably 16 minutes or more, more preferably 17 minutes or more, and further preferably 18 minutes or more, and can be 19 minutes or more or 20 minutes or more. There is no particular restriction on the upper limit of the above T75, and the longer the better, but it can be 60 minutes or less.

[0096] For the adhesive composition of the present invention, the water absorption X90, X25, X50 and X75 are determined as the increase in weight of the adhesive layer at the end point of each storage condition, when the weight of the adhesive layer in an absolutely dry state is set to 100%.

[0097] When the water absorption X90, X25, X50 and X75 reach the maximum value before reaching the end point of each storage condition, it indicates the saturated water absorption under each storage condition. On the other hand, when the maximum value is not reached before reaching the end point of each storage condition, it is not the saturated water absorption, but the end point of each storage condition is the maximum value. When the water absorption X90, X25, X50 and X75 are not the saturated water absorption, the water absorption speed is slow, which can prevent the rapid physical property change of the adhesive layer, so it is preferred, but it can also be the saturated water absorption.

[0098] For the adhesive composition of the present invention, the above-mentioned water absorption X90, X25, X50, X75, X90-X25, T90, T25, T50, T75 and T90 / T25 are specifically measured by the water absorption rate and water absorption rate measurement in the embodiments described later, and can be adjusted by, for example, the monomer composition (the type, content, composition, etc. of the functional group-containing monomer) of the base polymer (especially the acrylic polymer) described later, the type or amount of the cross-linking agent, the type or amount of the hydrogenated polyolefin resin, etc.

[0099] When the initial adhesion of the adhesive sheet of the present invention to the glass plate at 23°C, a pulling speed of 300 mm / min, a peeling angle of 180°, and a peeling length of 50 mm is set to Y0 (N / 20mm), there is no particular restriction on Y0. From the viewpoint of small changes in adhesion under storage conditions and excellent productivity, it is preferably 16N / 20mm or more, more preferably 17N / 20mm or more, further preferably 18N / 20mm or more, and further more preferably 19N / 20mm or more. There is no particular restriction on the upper limit value of the above Y0, but for example, it can be 60N / 20mm or less. It should be noted that in this specification, the above "initial adhesion" includes the value measured within 12 hours after the film formation of the adhesive layer.

[0100] When the initial adhesive force Y0 of the adhesive sheet of the present invention is measured, and the adhesive force of the adhesive sheet to the glass plate at 23°C, a pulling speed of 300 mm / min, a peeling angle of 180°, and a peeling length of 50 mm after being stored at 23°C and 50% RH for 48 hours is set to Y48 (N / 20mm), there is no particular restriction on Y48, but from the viewpoint of small change in adhesive force under storage environment and excellent productivity, it is preferably 16N / 20mm or more, more preferably 17N / 20mm or more, further preferably 18N / 20mm or more, and further more preferably 19N / 20mm or more. There is no particular restriction on the upper limit of the above Y48, but for example, it can be 60N / 20mm or less.

[0101] The rate of change ((Y0-Y48) / Y0×100)(%) of the adhesive force Y48 of the adhesive sheet of the present invention relative to the initial adhesive force Y0 is not particularly limited, but is preferably within ±10%, more preferably within ±9%, further preferably within ±8%, and may also be within ±7%, from the viewpoint of small change in adhesive force under storage environment and excellent productivity.

[0102] For the adhesive composition of the present invention, the above-mentioned adhesion Y0, Y48 and their change rate are specifically measured by the adhesion measurement in the embodiments described later, and can be adjusted by, for example, the monomer composition (type, content, composition, etc. of functional group-containing monomers) of the base polymer (especially acrylic polymer) described later, the type or amount of the cross-linking agent, the type or amount of the hydrogenated polyolefin resin, etc.

[0103] There is no particular restriction on the adhesive layer of the present invention. From the perspective of preventing malfunction of the touch panel having the adhesive layer, the dielectric constant is preferably controlled to be low. The dielectric constant of the adhesive layer of the present invention at a frequency of 100kHz is preferably 4 or less, more preferably 3.9 or less, and further preferably 3.8 or less. There is no particular restriction on the lower limit of the dielectric constant of the adhesive layer of the present invention at a frequency of 100kHz, but it is preferably 2.3 or more, more preferably 2.4 or more, and further preferably 2.5 or more.

[0104] The dielectric constant of the adhesive layer of the present invention is measured according to JIS K 6911, and can be adjusted by, for example, the monomer composition (type, content, composition, etc. of the functional group-containing monomer) of the base polymer (particularly acrylic polymer) described later, the type or amount of the crosslinking agent, the type or amount of the hydrogenated polyolefin resin, etc.

[0105] The pressure-sensitive adhesive layer of the present invention is used for bonding optical members of an image display device, and therefore has excellent transparency. Therefore, the visibility and appearance of the pressure-sensitive adhesive layer of the present invention are excellent.

[0106] The haze of the adhesive layer of the present invention (according to JIS K 7136) is not particularly limited, preferably 1.0% or less, more preferably 0.8% or less. When the haze is 1.0% or less, excellent transparency and excellent appearance are obtained, which is preferred. There is no particular restriction on the lower limit of the haze, but it is theoretically 0%, and it can be greater than 0.01% in practice. It should be noted that the above haze can be measured, for example, as follows: an adhesive layer (thickness: 100 μm) is made, and it is left to stand for at least 24 hours under normal conditions (23° C., 50% RH), and then attached to a slide glass (for example, a slide glass with a total transmittance of 92% and a haze of 0.2%), and the resulting product is used as a sample, and measured using a haze meter (manufactured by Murakami Color Technology Research Institute Co., Ltd., trade name "HM-150N") or its equivalent.

[0107] The total light transmittance (according to JIS K7361-1) of the adhesive layer of the present invention in the visible light wavelength range is not particularly limited, and is preferably 90% or more, more preferably 91% or more, and further preferably 92% or more. When the total light transmittance is 90% or more, excellent transparency and excellent appearance are obtained, which is preferred. There is no particular restriction on the upper limit of the total light transmittance, but in theory it is a value obtained by removing the light loss (Fresnel loss) caused by reflection generated at the air interface from 100%, and in practice it can be 95% or less. It should be noted that the above-mentioned total light transmittance can be measured, for example, as follows: an adhesive layer (thickness: 100 μm) is prepared, and the adhesive layer is allowed to stand at a normal temperature (23° C., 50% RH) for at least 24 hours, and then the release liner is peeled off in the case of a release liner, and the adhesive layer is attached to a slide glass (for example, a slide glass with a total light transmittance of 92% and a haze of 0.2%), and the resulting product is used as a sample and measured using a haze meter (manufactured by Murakami Color Technology Laboratory Co., Ltd., trade name "HM-150N") or its equivalent.

[0108] The thickness of the adhesive layer of the present invention is not particularly limited, and is preferably 12 μm to 350 μm, and more preferably 12 μm to 300 μm. When the thickness is above a certain value, it is preferred from the perspective of being able to fully relax the stress with the metal wiring in a touch panel having an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film, thereby preventing uneven display. In addition, when the thickness is below a certain value, operability and manufacturability are particularly excellent, which is preferred.

[0109] There is no particular limitation on the method for preparing the adhesive layer of the present invention. For example, the following method can be cited: preparing the adhesive composition (precursor composition) of the present invention, coating (applying) it on a substrate or a release liner, and irradiating with active energy rays, heating and drying, etc. as needed.

[0110] The adhesive composition of the present invention may have any form, for example, emulsion type, hot melt type (hot melt type), solvent-free type (active energy ray curing type, such as a monomer mixture, or a monomer mixture and its partial polymer, etc.). In particular, the adhesive composition of the present invention is preferably not a solvent type. This is because, when an adhesive layer is to be obtained using a solvent-type adhesive composition, it is easy to produce undesirable appearance such as orange peel wrinkles. It should be noted that "orange peel wrinkles" refers to the phenomenon of producing bumps like the skin of "pomelo", a kind of citrus fruit. In addition, from the viewpoint of obtaining an adhesive layer with excellent appearance, the adhesive composition of the present invention is preferably an active energy ray curing type. In this specification, an adhesive composition refers to a composition for forming an adhesive layer, including the meaning of a composition for forming an adhesive.

[0111] As described above, the adhesive composition of the present invention is preferably not a solvent-based composition, that is, preferably contains no organic solvent or substantially no organic solvent.

[0112] As the above-mentioned organic solvent, there is no particular limitation as long as it is an organic compound used as a solvent, and examples thereof include: hydrocarbon solvents such as cyclohexane, hexane, and heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; alcohol solvents such as methanol, ethanol, butanol, and isopropanol, etc. It should be noted that the above-mentioned organic solvent may be a mixed solvent containing two or more organic solvents.

[0113] In the adhesive composition of the present invention, "substantially free of" an organic solvent means that the organic solvent is not actively mixed except when the organic solvent is inevitably mixed in. Specifically, the adhesive composition can be said to be substantially free of an organic solvent when the content of the organic solvent in the adhesive composition is 1.0 wt % or less (preferably 0.5 wt % or less, more preferably 0.2 wt % or less) relative to the total amount of the adhesive composition (total weight, 100 wt %).

[0114] The adhesive composition of the present invention preferably does not contain or substantially does not contain halogen ions. The halogen ion concentration in the adhesive composition of the present invention is preferably 50 ppm or less. This configuration is preferred from the viewpoint of being able to obtain an anti-corrosion effect on metal wiring in a touch panel bonded with an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film. Relative to the total amount of the above-mentioned adhesive composition, the halogen ion content is preferably 50 ppm or less (for example, 0 to 50 ppm), more preferably 40 ppm or less (for example, 0 to 40 ppm), and further preferably 30 ppm or less (for example, 0 to 30 ppm) can be referred to as substantially free.

[0115] The adhesive composition of the present invention preferably does not contain or substantially does not contain a carboxyl group-containing monomer as a monomer component constituting the polymer. Therefore, in a touch panel bonded with an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, an anti-corrosion effect on the metal wiring can be obtained. The content of the carboxyl group-containing monomer is preferably 1 ng / cm relative to the total amount of the above-mentioned adhesive composition. 2 Below (for example, 0 to 1 ng / cm 2 ), more preferably 0.8 ng / cm 2 Below (for example, 0 to 0.8 ng / cm 2 ), more preferably 0.5 ng / cm 2 Below (for example, 0 to 0.5 ng / cm 2) can be said to be substantially free of. It should be noted that, as the above-mentioned carboxyl group-containing monomer, for example, (meth) acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc. can be cited, and in addition, the above-mentioned carboxyl group-containing monomer also includes anhydride group-containing monomers such as maleic anhydride and itaconic anhydride.

[0116] The halogen ion content and the carboxyl group-containing monomer content in the adhesive composition of the present invention can be measured by an energy dispersive fluorescent X-ray analyzer, ion chromatography, etc., and can be adjusted by, for example, the monomer composition (the type, content, composition, etc. of the functional group-containing monomer) of the base polymer (especially the acrylic polymer) described later, the type or amount of the cross-linking agent, the type or amount of the hydrogenated polyolefin resin, etc.

[0117] As the base polymer contained in the adhesive composition of the present invention, there is no particular restriction, for example, it can be listed: acrylic polymers contained as base polymers in acrylic adhesive layers, rubber polymers contained as base polymers in rubber adhesive layers (natural rubber adhesive layers, synthetic rubber adhesive layers, etc.), silicone polymers contained as base polymers in silicone adhesive layers, polyester polymers contained as base polymers in polyester adhesive layers, carbamate polymers contained as base polymers in carbamate adhesive layers, polyamide polymers contained as base polymers in polyamide adhesive layers, epoxy polymers contained as base polymers in epoxy adhesive layers, vinyl alkyl ether polymers contained as base polymers in vinyl alkyl ether adhesive layers, fluorine-containing polymers contained as base polymers in fluorine-containing adhesive layers, etc. Among them, from the perspectives of transparency, weather resistance, adhesive reliability, and the ease of functional design of the adhesive layer due to the rich variety of monomers, the above-mentioned base polymer is preferably an acrylic polymer. That is, the adhesive composition of the present invention is preferably an acrylic adhesive composition containing the acrylic polymer described later as a base polymer. In addition, the base polymer can be used individually or in combination of 2 or more types.

[0118] The content of the base polymer in the adhesive composition of the present invention is not particularly limited, but is preferably 75 wt % or more (eg, 75 to 99.9 wt %), and more preferably 85 wt % or more (eg, 85 to 99.9 wt %).

[0119] When the pressure-sensitive adhesive composition of the present invention is an acrylic pressure-sensitive adhesive composition containing an acrylic polymer as a base polymer, it is referred to as "the acrylic pressure-sensitive adhesive composition of the present invention."

[0120] Hereinafter, the acrylic pressure-sensitive adhesive composition of the present invention will be described in detail, but the present invention is not limited thereto.

[0121] [1-1. Acrylic polymer]

[0122] The acrylic adhesive composition of the present invention is an adhesive composition containing an acrylic polymer as a base polymer. It should be noted that the acrylic polymer can be used alone or in combination of two or more. In addition to the acrylic polymer, the acrylic adhesive composition of the present invention may also contain a hydrogenated polyolefin resin, a multifunctional (meth)acrylate, a silane coupling agent, and other additives described below.

[0123] The content of the acrylic polymer is not particularly limited, but is preferably 60 wt % or more (e.g., 60 to 99.9 wt %), and more preferably 70 wt % or more (e.g., 70 to 99.9 wt %), relative to the total weight (total weight, 100 wt %) of the acrylic pressure-sensitive adhesive composition of the present invention.

[0124] The acrylic adhesive composition of the present invention that forms the adhesive layer containing the acrylic polymer as the main component is not particularly limited, and examples thereof include: a composition containing the acrylic polymer as an essential component; a composition containing a mixture of monomer components constituting the acrylic polymer (sometimes referred to as a "monomer mixture") or a partial polymer thereof as an essential component, etc. There are no particular restrictions, and examples of the former include so-called water-dispersible compositions (emulsion compositions), etc., and examples of the latter include so-called active energy ray-curable compositions, etc. Among them, the acrylic adhesive composition of the present invention is preferably a composition containing a monomer mixture or a partial polymer thereof as an essential component.

[0125] In this specification, the above-mentioned "mixture of monomer components" includes the case where it is composed of a single monomer component and the case where it is composed of two or more monomer components. In addition, the above-mentioned "partial polymer of a mixture of monomer components" refers to a composition in which one or more monomer components among the constituent monomer components of the above-mentioned "mixture of monomer components" are partially polymerized.

[0126] In this specification, when referring to "acrylic polymer", unless otherwise specified, it includes "acrylic polymer", "mixture of monomer components constituting acrylic polymer" and "partial polymer of the mixture of monomer components constituting acrylic polymer".

[0127] The acrylic polymer is a polymer containing a structural unit derived from an acrylic monomer as a structural unit. It should be noted that in this specification, "(meth)acrylic acid" means either or both of "acrylic acid" and "methacrylic acid", and the same applies to others. The weight average molecular weight of the acrylic polymer is not particularly limited, but is preferably 100,000 to 5,000,000.

[0128] In the acrylic pressure-sensitive adhesive composition of the present invention, the acrylic polymer is preferably a polymer containing, as a monomer unit, an alkyl (meth)acrylate having a linear or branched alkyl group (hereinafter sometimes simply referred to as “alkyl (meth)acrylate”).

[0129] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate (n-butyl (meth)acrylate), isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, and tert-butyl (meth)acrylate. Alkyl (meth)acrylates having an alkyl group with 1 to 24 carbon atoms, such as nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, etc. It should be noted that the alkyl (meth)acrylates may be used alone or in combination of two or more.

[0130] As the alkyl (meth)acrylate, alkyl acrylate is preferred over alkyl methacrylate in that the polymerization time of the acrylic polymer can be shortened to improve productivity. In particular, when the acrylic polymer of the present invention is cured by radiation polymerization, alkyl acrylate is preferred.

[0131] Among them, from the viewpoint of obtaining strong adhesion and adjusting residual stress, the above-mentioned alkyl (meth)acrylate is preferably an alkyl (meth)acrylate having an alkyl group with 1 to 18 carbon atoms, more preferably methyl methacrylate (MMA), butyl acrylate (BA), 2-ethylhexyl acrylate (2EHA), and isostearyl acrylate (ISTA), and more preferably 2-ethylhexyl acrylate (2EHA) and isostearyl acrylate (ISTA).

[0132] The content (ratio) of the alkyl (meth)acrylate in all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. From the viewpoint of improving durability and obtaining high adhesive reliability, the content of the alkyl (meth)acrylate is preferably 30 to 90 parts by weight, more preferably 35 to 85 parts by weight, and even more preferably 40 to 80 parts by weight, relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer.

[0133] It should be noted that, in this specification, the term "the total amount of monomer components constituting the acrylic polymer" also includes monomer components added to the acrylic adhesive composition containing the acrylic polymer in the acrylic adhesive composition of the present invention for the purpose of adjusting the elastic modulus of the adhesive layer, etc.

[0134] As a preferred embodiment of the acrylic adhesive composition of the present invention, the acrylic polymer is preferably a polymer containing an alkyl (meth)acrylate having an alkyl group with 8 or more carbon atoms (sometimes referred to as "alkyl (meth)acrylate (A)") as an essential monomer unit. The acrylic polymer can realize a highly flexible adhesive layer by the action of the above-mentioned medium-chain to long-chain alkyl group, and even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, the stress on the metal wiring can be fully relaxed, thereby preventing display unevenness, and is therefore preferred.

[0135] In the present embodiment, examples of the alkyl (meth)acrylate (A) include alkyl (meth)acrylates having an alkyl group with 8 or more carbon atoms (preferably 8 to 24 carbon atoms) such as octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate. The alkyl (meth)acrylate (A) may be used alone or in combination of two or more.

[0136] In the present embodiment, as the (meth)acrylic acid alkyl ester (A), an alkyl acrylate is preferred over an alkyl methacrylate in that the polymerization time of the acrylic polymer (A) can be shortened to improve productivity. In particular, when the acrylic polymer of the present invention is cured by radiation polymerization, an alkyl acrylate is preferred.

[0137] Among them, as the (meth) alkyl acrylate (A), from the perspective of being able to realize a highly flexible adhesive layer and being able to fully relax the stress with the metal wiring even when laminating an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film, thereby preventing uneven display, it is preferred to include a (meth) alkyl acrylate having a branched alkyl group with a carbon number of 8 or more, preferably an (meth) alkyl acrylate having a branched alkyl group with a carbon number of 8 or 9, further preferably 2-ethylhexyl (meth) acrylate, and particularly preferably 2-ethylhexyl acrylate (2EHA). The number of carbon atoms of the side chain alkyl group of the above-mentioned branched alkyl group is not particularly limited, and an alkyl group having a carbon number of 1 to 3 (e.g., methyl, ethyl, n-propyl, isopropyl) is preferred. "Side chain alkyl" is an alkyl group substituted on the side chain of the carbon chain with the longest carbon number.

[0138] In the present embodiment, the content (ratio) of the above-mentioned (meth)acrylate (A) in all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. From the perspective of being able to realize a highly flexible adhesive layer and being able to sufficiently relax the stress on the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, thereby preventing display unevenness, the content of the above-mentioned (meth)acrylate (A) is preferably 30 to 99 parts by weight, more preferably 35 to 95 parts by weight, and even more preferably 40 to 90 parts by weight relative to the total amount (100 parts by weight) of the monomer components constituting the acrylic polymer.

[0139] In the present embodiment, when the (meth)acrylate alkyl ester (A) contains an (meth)acrylate alkyl ester having a branched alkyl group having 8 or 9 carbon atoms (hereinafter, in the present specification, sometimes referred to as (meth)acrylate alkyl ester (A1)), it is preferred that the (meth)acrylate alkyl ester (A) further contains an (meth)acrylate alkyl ester having a branched alkyl group having 10 to 24 carbon atoms (hereinafter, in the present specification, sometimes referred to as (meth)acrylate alkyl ester (A2)).

[0140] In the present embodiment, when the (meth)acrylate alkyl ester (A) contains an alkyl (meth)acrylate (A2) in addition to the alkyl (meth)acrylate (A1), the dielectric constant of the adhesive layer of the present invention can be reduced by the action of the long-chain branched alkyl group. Even when attached to an optical member (touch sensor film) having a metal wiring layer such as a metal mesh wiring or silver nanowire, the adhesive layer has a low dielectric constant and can prevent erroneous operation, which is preferred from this point of view.

[0141] The Tg of the homopolymer of the (meth) alkyl acrylate (A2) is preferably -80°C to 0°C, and more preferably -70°C to -10°C. When the Tg of the homopolymer is below -80°C, the elastic modulus of the adhesive layer at room temperature sometimes decreases excessively, which is not preferred. When the Tg of the homopolymer exceeds 0°C, the adhesive force sometimes decreases, which is not preferred. The Tg of the homopolymer is a value measured by a differential scanning calorimeter (DSC). In addition, regarding the branched alkyl group having 10 to 24 carbon atoms, although the carbon number is 10 to 24 from the aspect of being able to satisfy the appropriate low dielectric constant and elastic modulus, the (meth) alkyl acrylate having a preferred alkyl group can be appropriately selected according to the method for producing the (meth) acrylic polymer. For example, in the case of producing a (meth) acrylic polymer by solution polymerization, the above-mentioned alkyl group is more preferably 10 to 18 carbon atoms, more preferably 10 to 16 carbon atoms, and more preferably 10 to 14 carbon atoms. When the acrylic polymer is produced by radiation polymerization or the like, the alkyl group preferably has 12 to 18 carbon atoms, and more preferably has 14 to 18 carbon atoms.

[0142] Examples of the (meth)acrylic acid alkyl ester (A2) include isodecyl acrylate (having 10 carbon atoms, Tg of homopolymer = -60°C, hereinafter referred to as Tg), isodecyl methacrylate (having 10 carbon atoms, Tg = -41°C), isomyristyl acrylate (having 14 carbon atoms, Tg = -56°C), isostearyl acrylate (having 18 carbon atoms, Tg = -18°C), 2-propylheptyl acrylate, isondecyl acrylate, isododecyl acrylate, isotridecyl acrylate, isopentadecyl acrylate, isohexadecyl acrylate, isoheptadecyl acrylate, and the methacrylic acid ester monomers exemplified above. The (meth)acrylic acid alkyl ester (A2) can be used alone or in combination of two or more.

[0143] In addition, among the branched alkyl groups having 10 to 24 carbon atoms, when a branched alkyl group such as a tert-butyl group is present at the end of the ester group, it is particularly preferred in that the molar volume is increased and the dipole moment is decreased, thereby obtaining an adhesive layer having a balance between the two. As the branched alkyl group at the end of the ester group, a branched alkyl group having 4 to 6 carbon atoms such as a tert-butyl group, a neopentyl group, and a tert-amyl group is preferred, and a tert-butyl group is particularly preferred. As a preferred example of the (meth)acrylic acid alkyl ester (A2) having a tert-butyl group at the end of the ester group, isostearyl acrylate represented by the following formula can be cited.

[0144]

[0145] In the present embodiment, the content (ratio) of the above-mentioned (meth) alkyl acrylate (A1) in all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. From the perspective of being able to realize a highly flexible adhesive layer, even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is attached, the stress with the metal wiring can be fully relaxed, thereby preventing uneven display. The content of the above-mentioned (meth) alkyl acrylate (A1) is preferably 30 parts by weight or more, more preferably 35 parts by weight or more, further preferably 40 parts by weight or more, and can also be 45 parts by weight or more, relative to the total amount of monomer components constituting the acrylic polymer (100 parts by weight). In addition, from the perspective of making the adhesive layer low in dielectric constant to prevent erroneous operation, the above-mentioned content is preferably 70 parts by weight or less, more preferably 65 parts by weight or less, and further preferably 60 parts by weight or less.

[0146] In the present embodiment, the content (ratio) of the above-mentioned (meth) alkyl acrylate (A2) in all monomer units of the acrylic polymer (total amount of monomer components constituting the acrylic polymer is 100 parts by weight) is not particularly limited. From the perspective of reducing the dielectric constant of the adhesive layer to prevent erroneous operation, the content of the above-mentioned (meth) alkyl acrylate (A2) is preferably 10 parts by weight or more, more preferably 15 parts by weight or more, and further preferably 20 parts by weight or more, and can be 30 parts by weight or more or 40 parts by weight or more. In addition, from the perspective of being able to achieve a highly flexible adhesive layer, and being able to fully relax the stress with the metal wiring even when laminating an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film, thereby preventing uneven display, the above-mentioned content is preferably 50 parts by weight or less, more preferably 40 parts by weight or less, further preferably 35 parts by weight or less, and particularly preferably 30 parts by weight or less.

[0147] The weight ratio ((meth) acrylate (A2) / (meth) acrylate (A1)) of the above-mentioned alkyl (meth) acrylate (A1) and alkyl (meth) acrylate (A2) in the acrylic polymer of the present embodiment is not particularly limited. From the perspective of being able to achieve a highly flexible adhesive layer and being able to fully relax the stress with the metal wiring even when an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, thereby preventing uneven display, the above-mentioned ratio is preferably 2 or less, more preferably 1.5 or less, further preferably 1 or less, particularly preferably 0.5 or less, and may also be 0.45 or less. In addition. From the perspective of making the adhesive layer low in dielectric constant to prevent misoperation, the above-mentioned ratio is preferably 0.2 or more, more preferably 0.25 or more, further preferably 0.3 or more, and may also be 0.35 or more.

[0148] In the present embodiment, the acrylic polymer may contain an alkyl (meth)acrylate other than the alkyl (meth)acrylate (A) (hereinafter sometimes referred to as "alkyl (meth)acrylate (B)") as a monomer component. Examples of the alkyl (meth)acrylate (B) include alkyl (meth)acrylates having a linear or branched alkyl group having 1 to 7 carbon atoms. The alkyl (meth)acrylate (B) may be used alone or in combination of two or more.

[0149] In the present embodiment, the content (ratio) of the above-mentioned (meth)acrylate alkyl ester (B) in all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer) is not particularly limited. From the perspective of being able to realize a highly flexible adhesive layer and being able to sufficiently relax the stress with the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, thereby preventing display unevenness, the content of the above-mentioned (meth)acrylate alkyl ester (B) is preferably 10 parts by weight or less, and more preferably 5 parts by weight or less, relative to the total amount of monomer components constituting the acrylic polymer (100 parts by weight).

[0150] In the acrylic adhesive composition of the present invention, the acrylic polymer may contain, in addition to the above-mentioned alkyl (meth)acrylate (including alkyl (meth)acrylate (A) and alkyl (meth)acrylate (B)), a copolymerizable functional group-containing monomer (copolymerizable functional group-containing monomer) as a monomer unit. That is, the acrylic polymer may contain a functional group-containing monomer as a constituent monomer component. It should be noted that the functional group-containing monomer may be used alone or in combination of two or more.

[0151] The content (ratio) of the above-mentioned functional group-containing monomer relative to the total amount of monomer components constituting the acrylic polymer (100 parts by weight) is not particularly limited. From the perspective of obtaining an adhesive layer having high reliability that the adhesive strength is not easily changed due to environmental changes, small changes in the adhesive strength caused by the storage environment immediately after film formation, and excellent productivity, the content of the above-mentioned functional group-containing monomer is preferably 5 to 40 parts by weight, more preferably 10 to 30 parts by weight, and further preferably 15 to 25 parts by weight.

[0152] As the above-mentioned functional group-containing monomer, there is no particular restriction. From the perspective of controlling the above-mentioned various characteristics of the adhesive layer (especially water absorption rate, water absorption speed, etc.) within a specified range, obtaining a highly reliable adhesive layer whose adhesive force is not easily changed relative to environmental changes, adhesion reliability, compatibility with various additives such as ultraviolet absorbers, and transparency, preferably, monomers having nitrogen atoms in the molecule (referred to as "nitrogen-containing monomers") and monomers having hydroxyl groups in the molecule (referred to as "hydroxyl-containing monomers") can be cited. That is, the above-mentioned acrylic polymer preferably contains nitrogen-containing monomers as structural units. In addition, the above-mentioned acrylic polymer preferably contains hydroxyl-containing monomers as structural units.

[0153] When the acrylic polymer contains a nitrogen-containing monomer as a monomer unit, it is easy to obtain moderate cohesive force, so it is easy to increase the 180° peeling adhesion to the glass plate, thereby easily obtaining strong adhesiveness and excellent anti-foaming peeling property. In addition, the adhesive layer is easy to obtain moderate flexibility, and the 300% tensile residual stress is adjusted to a specific range. Even when an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film is attached, the stress with the metal wiring can be fully relaxed, thereby preventing display unevenness.

[0154] In the case where the acrylic polymer contains the nitrogen-containing monomer as a monomer component constituting the polymer, the proportion of the nitrogen-containing monomer in all monomer components (100% by weight) constituting the acrylic polymer is not particularly limited, preferably 1% by weight or more, more preferably 3% by weight or more, further preferably 5% by weight or more, and can be 10% by weight or more or 15% by weight or more. When the above-mentioned proportion is 1% by weight or more, it is preferred from the perspective of controlling the above-mentioned various characteristics (especially water absorption, water absorption rate, etc.) of the adhesive layer within a specified range, obtaining an adhesive layer with high reliability that is not easy to change with respect to environmental changes, and being able to obtain high adhesive reliability. In addition, from the perspective of obtaining an adhesive layer with moderate softness, obtaining an adhesive layer with excellent transparency, controlling the above-mentioned various characteristics (especially water absorption, water absorption rate, etc.) of the adhesive layer within a specified range, and obtaining an adhesive layer with high reliability that is not easy to change with respect to environmental changes, the upper limit of the proportion of the nitrogen-containing monomer is preferably 30% by weight or less, more preferably 25% by weight or less, and further preferably 20% by weight or less.

[0155] When the acrylic polymer contains a hydroxyl group-containing monomer as a monomer unit, polymerization can be easily performed when the monomer components are polymerized, and good cohesive force can be easily obtained. Therefore, strong adhesiveness can be easily obtained, and excellent anti-foaming and peeling properties can be easily obtained.

[0156] In the case where the acrylic polymer contains the hydroxyl-containing monomer as a monomer component constituting the polymer, the proportion of the hydroxyl-containing monomer in the total monomer components (100% by weight) constituting the acrylic polymer is not particularly limited, and is preferably 10% by weight or less. When the acrylic polymer contains a large amount of hydroxyl-containing monomer, the affinity of the hydroxyl group to water is high, so there is a tendency for the water absorption of the adhesive layer to become higher. The configuration in which the proportion of the hydroxyl-containing monomer in the acrylic polymer is 10% by weight or less is preferred in terms of controlling the variation of the water absorption rate of the adhesive layer of the present invention caused by the environment to be relatively low, thereby obtaining an adhesive layer with high reliability that is not easy to change with respect to environmental changes, small variation of the adhesive force caused by the storage environment just after film formation, and excellent productivity.

[0157] The proportion of the hydroxyl-containing monomer is preferably 8% by weight or less, and more preferably 6% by weight or less, from the perspective of controlling the change in water absorption rate of the adhesive layer of the present invention caused by the environment to be low, thereby obtaining an adhesive layer with high reliability that is not easy to change in adhesion relative to environmental changes, small change in adhesion caused by the storage environment just after film formation, and excellent productivity. In addition, the lower limit of the proportion of the hydroxyl-containing monomer is not particularly limited, but is preferably 0.5% by weight or more, more preferably 0.8% by weight or more, and more preferably 1% by weight or more, from the perspective of obtaining high adhesion reliability and becoming a reaction site with a cross-linking agent.

[0158] The total proportion of the nitrogen-atom-containing monomer and the hydroxyl-containing monomer in all monomer components (100% by weight) constituting the acrylic polymer is not particularly limited, but is preferably 5% by weight or more, more preferably 10% by weight or more, and further preferably 15% by weight or more, from the perspective of obtaining a highly reliable adhesive layer whose adhesive force is not easily changed with respect to environmental changes and obtaining high adhesive reliability. In addition, from the perspective of obtaining an adhesive layer with moderate flexibility, obtaining an adhesive layer with excellent transparency, and facilitating the control of the above-mentioned various properties (especially water absorption, water absorption speed, etc.) of the adhesive layer within a specified range, the upper limit of the total proportion is preferably 40% by weight or less, more preferably 30% by weight or less, and further preferably 25% by weight or less.

[0159] The ratio of the nitrogen-containing monomer to the hydroxyl-containing monomer in the acrylic polymer (nitrogen-containing monomer / hydroxyl-containing monomer) is not particularly limited, and is preferably 1 to 50, more preferably 1.5 to 40, further preferably 2 to 30, and particularly preferably 2 to 25. A configuration in which the ratio is 1 or more is preferred from the perspective of controlling the variation in water absorption of the adhesive layer of the present invention caused by the environment to be low, thereby obtaining an adhesive layer having high reliability that is not easily changed in adhesive force due to environmental changes, small variation in adhesive force caused by the storage environment immediately after film formation, and excellent productivity. In addition, a configuration in which the ratio is 50 or less is preferred from the perspective of enabling the hydroxyl group derived from the hydroxyl-containing monomer to become a reaction site of a crosslinking agent described later.

[0160] The acrylic polymer can be obtained by polymerizing the monomer units (monomer components) using a known or customary polymerization method. Examples of the polymerization method for the acrylic polymer include a solution polymerization method, an emulsion polymerization method, a bulk polymerization method, and a polymerization method using active energy ray irradiation (active energy ray polymerization method). Among them, from the perspective of transparency, water resistance, cost, etc. of the adhesive layer, the solution polymerization method and the active energy ray polymerization method are preferred, and the active energy ray polymerization method is more preferred.

[0161] When the acrylic polymer is polymerized, various common solvents can be used. The solvents can be used alone or in combination of two or more.

[0162] In addition, when polymerizing the acrylic polymer, a polymerization initiator such as a thermal polymerization initiator or a photopolymerization initiator (photoinitiator) may be used depending on the type of polymerization reaction. The polymerization initiator may be used alone or in combination of two or more.

[0163] The amount of the photopolymerization initiator used is not particularly limited. For example, relative to 100 parts by weight of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer), the amount of the photopolymerization initiator used is preferably 0.001 to 1 part by weight, and more preferably 0.01 to 0.50 parts by weight.

[0164] [1-2. Hydroxyl-containing monomers]

[0165] Hydroxyl-containing monomer refers to a monomer having at least one hydroxyl group in the molecule. In addition, a monomer having at least one hydroxyl group in the molecule and at least one carboxyl group in the molecule is a carboxyl-containing monomer, rather than a hydroxyl-containing monomer. As the above-mentioned hydroxyl-containing monomer, there is no particular restriction. From the viewpoint of being easy to obtain good cohesive force and easy to obtain adhesive reliability at high temperature, hydroxyl-containing (meth) acrylates are preferred, and 2-hydroxyethyl acrylate (HEA), 2-hydroxypropyl acrylate (HPA), 4-hydroxybutyl acrylate (4-HBA) are more preferred. It should be noted that the hydroxyl-containing monomer can be used alone or in combination of two or more.

[0166] [1-3. Nitrogen atom-containing monomer]

[0167] A nitrogen atom-containing monomer refers to a monomer having at least one nitrogen atom in the molecule (in one molecule). Among them, the above-mentioned nitrogen atom-containing monomer is not included in the above-mentioned hydroxyl-containing monomer. That is, in this specification, a monomer having a hydroxyl group and a nitrogen atom in the molecule is included in the nitrogen atom-containing monomer. In addition, a monomer having at least one nitrogen atom in the molecule and at least one carboxyl group in the molecule is a carboxyl-containing monomer, rather than a nitrogen atom-containing monomer. As the above-mentioned nitrogen atom-containing monomer, from the viewpoint of improving the resistance to foaming and peeling, N-vinyl cyclic amide, (methyl) acrylamide, etc. are preferred. It should be noted that the nitrogen atom-containing monomer can be used alone or in combination of two or more.

[0168] As the N-vinyl cyclic amide, an N-vinyl cyclic amide represented by the following formula (1) is preferred from the viewpoint of easily obtaining good cohesive force and easily obtaining high-temperature adhesive reliability.

[0169]

[0170] (In formula (1), R 1 represents a divalent organic group. )

[0171] In the above formula (1), R 1 It is a divalent organic group, preferably a divalent saturated hydrocarbon group or a divalent unsaturated hydrocarbon group, and more preferably a divalent saturated hydrocarbon group (for example, an alkylene group having 3 to 5 carbon atoms).

[0172] As the N-vinyl cyclic amide represented by the above formula (1), from the viewpoint of further improving the foaming and peeling resistance, N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3- More preferred are oxazine-2-one, N-vinyl-3,5-morpholinedione, etc., more preferred are N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam, and further preferred is N-vinyl-2-pyrrolidone.

[0173] [1-4. Other copolymerizable monomers]

[0174] Examples of copolymerizable monomers in acrylic polymers include, in addition to the above-mentioned nitrogen atom-containing monomers and hydroxyl-containing monomers, alicyclic structure-containing monomers, epoxy group-containing monomers, (meth)acrylic acid alkoxyalkyl esters, epoxy group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, (meth)acrylic acid esters having aromatic hydrocarbon groups, vinyl esters, aromatic vinyl compounds, olefins or dienes, vinyl ethers, vinyl chloride, and the like.

[0175] [1-5. Hydrogenated polyolefin resin]

[0176] The acrylic adhesive composition of the present invention is preferably an acrylic adhesive composition with an acrylic polymer as the main component and a hydrogenated polyolefin resin. The hydrogenated polyolefin resin is a material with a low dielectric constant. By being matched to the acrylic polymer of the present invention, the dielectric constant can be reduced, so that in a touch panel with an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, the erroneous operation of the touch operation can be suppressed. In addition, it is possible to realize an adhesive layer with high flexibility without the need for low molecular weight of the acrylic polymer, and even in the case of an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, it is possible to fully relax the stress with the metal wiring, thereby preventing uneven display, which is preferred from this aspect. In addition, the compatibility of the hydrogenated polyolefin resin and the acrylic polymer is also excellent, so it is preferred from the aspect of being able to maintain the transparency of the adhesive layer of the present invention at a higher level. The hydrogenated polyolefin resin can be used alone or in combination of two or more.

[0177] The hydrogenated polyolefin resin preferably exhibits liquid fluidity at 25° C. from the viewpoint of being able to realize a highly flexible adhesive layer and being able to sufficiently relax the stress with the metal wiring even when an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is bonded, thereby preventing display unevenness. The hydrogenated polyolefin resin exhibiting liquid fluidity at 25° C. means that the viscosity measured at 25° C. using a B-type viscometer is 10,000 mPa·s or less.

[0178] Since the hydrogenated polyolefin resin has fewer carbon-carbon double bonds in its molecule, it is less likely to be inhibited from polymerization when the acrylic adhesive composition of the present invention is cured by ultraviolet irradiation, and is less likely to undergo a decrease in polymerization rate or a decrease in molecular weight, so that the adhesive reliability of the acrylic adhesive composition of the present invention at high temperatures can be maintained at a high level.

[0179] From the viewpoint of being less likely to cause inhibition of polymerization and adhesive reliability at high temperatures, the hydrogenation rate of the hydrogenated polyolefin resin is preferably 90% or more, more preferably 95% or more, and even more preferably 97% or more. The upper limit of the hydrogenation rate is not particularly limited, but is theoretically 100%, and in practice can be 99.9% or less, or 99.8% or less. It should be noted that the hydrogenation rate of the hydrogenated polyolefin resin can be adjusted by using 1 The H-NMR measurement can be used to determine the amount of double bonds remaining in the hydrogenated polyolefin resin.

[0180] From the viewpoint of being less likely to cause inhibition and adhesive reliability at high temperatures, the iodine value (Ig / 100g) of the hydrogenated polyolefin resin is preferably 30 or less, more preferably 25 or less, and further preferably 20 or less. The lower limit of the iodine value is not particularly limited, but may be 0.1 or more, or 0.2 or more. It should be noted that the iodine value is a value measured in accordance with JIS K 0070-1992.

[0181] The number average molecular weight (Mn) of the hydrogenated polyolefin resin is preferably 1000 to 5000 from the viewpoint of imparting appropriate stress relaxation and fluidity to the adhesive layer and improving compatibility with the acrylic polymer. The number average molecular weight (Mn) is preferably 1000 or more, more preferably 1500 or more, and further preferably 1800 or more from the viewpoint of imparting appropriate stress relaxation and fluidity to the adhesive composition. The number average molecular weight (Mn) is preferably 5000 or less, more preferably 4800 or less, and further preferably 4600 or less from the viewpoint of improving compatibility with the acrylic polymer and maintaining the transparency of the acrylic adhesive composition of the present invention at a higher level.

[0182] From the perspective of imparting appropriate stress relaxation and fluidity to the adhesive layer, improving compatibility with acrylic polymers, maintaining high transparency, and suppressing haze, the polydispersity (Mw / Mn) of the hydrogenated polyolefin resin is preferably 2.0 or less, more preferably 1.8 or less. The lower limit of the polydispersity is not particularly limited, but can be 1.0 or 1.1 or more in practical use.

[0183] The number average molecular weight (Mn) and polydispersity (Mw / Mn) of the hydrogenated polyolefin resin are values ​​determined by measuring by gel permeation chromatography (GPC) based on polystyrene standards.

[0184] The hydrogenated polyolefin resin includes hydrogenated polyolefin. The acrylic pressure-sensitive adhesive composition of the present invention preferably includes hydrogenated polyolefin as the hydrogenated polyolefin resin, from the viewpoint of lowering the dielectric constant and suppressing erroneous operation of touch operation in the touch panel.

[0185] The hydrogenated polyolefin is a hydrogenated product of a polymer (polyolefin) having a structural unit derived from an olefin. The hydrogenated polyolefin includes hydrogenated products of homopolymers and copolymers of α-olefins such as ethylene, propylene, 1-butene, isobutylene, and 1-hexene; diene compounds such as butadiene and isoprene; and aromatic vinyl compounds such as styrene. As the hydrogenated polyolefin, the hydrogenated product of the homopolymer or copolymer of the diene compound is preferred, for example, hydrogenated polybutadiene, hydrogenated polyisoprene, etc. The hydrogenated polyolefin can be used alone or in combination of two or more.

[0186] From the viewpoint of reducing the dielectric constant and suppressing erroneous operation of touch operation in the touch panel, the hydrogenated polyolefin-based resin preferably contains a hydrogenated polyolefin polyol in addition to the hydrogenated polyolefin.

[0187] The hydrogenated polyolefin polyol is a compound obtained by modifying the terminal of the hydrogenated polyolefin with a hydroxyl group. As the hydrogenated polyolefin polyol, a hydroxyl-modified product of a hydrogenated product of a homopolymer or copolymer of a diene compound is preferred, for example, hydrogenated polybutadiene polyol, hydrogenated polyisoprene polyol, etc. The hydrogenated polyolefin polyol can be used alone or in combination of two or more.

[0188] As the above-mentioned hydrogenated polyolefin and hydrogenated polyolefin polyol, hydrogenated polybutadiene and hydrogenated polybutadiene polyol are respectively preferred from the perspective of being able to realize a highly flexible adhesive layer and being able to fully relax the stress with the metal wiring even when an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film is bonded, thereby preventing display unevenness.

[0189] As the hydrogenated polybutadiene, a hydrogenated polybutadiene represented by the following formula (2) is preferred, and as the hydrogenated polybutadiene polyol, a hydrogenated polybutadiene polyol represented by the following formula (3) is preferred.

[0190]

[0191] In the above formula, m represents the degree of polymerization of the hydrogenated polybutadiene.

[0192] As hydrogenated polyolefins and hydrogenated polyolefin polyols, commercial products can be used. Commercial products of hydrogenated polyolefins include: trade names "BI-2000", "BI-3000" (all manufactured by Nippon Soda Co., Ltd.), etc. Commercial products of hydrogenated polyolefin polyols include: trade names "GI-1000", "GI-2000", "GI-3000" (all manufactured by Nippon Soda Co., Ltd.), trade name "EPOL" (manufactured by Idemitsu Kosan Co., Ltd.), etc.

[0193] The content of the hydrogenated polyolefin resin in the acrylic adhesive composition is not particularly limited. From the perspective of reducing the dielectric constant and thus suppressing erroneous operation of the touch operation of the touch panel, the content of the hydrogenated polyolefin resin is preferably 5 parts by weight or more, more preferably 10 parts by weight or more, and further preferably 15 parts by weight or more relative to 100 parts by weight of the acrylic polymer. On the other hand, from the perspective of suppressing the increase in haze and ensuring higher transparency, and from the perspective of being able to highly maintain the adhesive force and adhesive reliability at high temperatures, the content of the hydrogenated polyolefin resin is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, and further preferably 30 parts by weight or less.

[0194] The content of hydrogenated polyolefin in the acrylic adhesive composition is not particularly limited. From the viewpoint of reducing the dielectric constant and thus suppressing the erroneous operation of the touch operation of the touch panel, the content of hydrogenated polyolefin is preferably 0.5 parts by weight or more, more preferably 1 part by weight or more, and further preferably 1.5 parts by weight or more relative to 100 parts by weight of the acrylic polymer. On the other hand, from the viewpoint of suppressing the increase of haze and ensuring higher transparency, and from the viewpoint of being able to highly maintain the adhesive force and adhesive reliability at high temperatures, the content of hydrogenated polyolefin is preferably 20 parts by weight or less, more preferably 15 parts by weight or less, and further preferably 12 parts by weight or less.

[0195] The content of the hydrogenated polyolefin polyol in the acrylic adhesive composition is not particularly limited. From the perspective of reducing the dielectric constant and thus suppressing the erroneous operation of the touch operation of the touch panel, the content of the hydrogenated polyolefin polyol is preferably 1 part by weight or more, more preferably 3 parts by weight or more, further preferably 5 parts by weight or more, and may be 10 parts by weight or more relative to 100 parts by weight of the acrylic polymer. On the other hand, from the perspective of suppressing the increase in haze and ensuring higher transparency, and from the perspective of being able to highly maintain the adhesive force and adhesive reliability at high temperatures, the content of the hydrogenated polyolefin polyol is preferably 40 parts by weight or less, more preferably 35 parts by weight or less, further preferably 30 parts by weight or less, and particularly preferably 25 parts by weight or less.

[0196] The weight ratio of the content of hydrogenated polyolefin to the content of hydrogenated polyolefin polyol in the acrylic adhesive composition (hydrogenated polyolefin / hydrogenated polyolefin polyol) is not particularly limited. From the perspective of reducing the dielectric constant and thus suppressing the erroneous operation of the touch operation of the touch panel, it is preferably 1 / 99 or more, more preferably 2 / 98 or more, and can be 3 / 97 or more or 4 / 96 or more. In addition, from the perspective of suppressing the increase of haze and ensuring higher transparency, the above ratio is preferably 90 / 10 or less, more preferably 80 / 20 or less, further preferably 70 / 30 or less, and can be 55 / 45 or less, 45 / 55 or less, or 30 / 70 or less.

[0197] [1-6. Multifunctional (meth)acrylate]

[0198] The acrylic pressure-sensitive adhesive composition of the present invention preferably further contains a polyfunctional (meth)acrylate. The polyfunctional (meth)acrylate functions as a crosslinking component, and the pressure-sensitive adhesive composition tends to have appropriate cohesive strength.

[0199] Examples of the multifunctional (meth)acrylate include hexanediol di(meth)acrylate, butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, and urethane acrylate. It should be noted that the multifunctional (meth)acrylate may be used alone or in combination of two or more.

[0200] The content (ratio) of the multifunctional (meth) acrylate is not particularly limited. From the viewpoint that the adhesive layer has a moderate cohesive force, the content (ratio) of the multifunctional (meth) acrylate is preferably 0.001 parts by weight or more, more preferably 0.002 parts by weight or more, further preferably 0.005 parts by weight or more, and can be 0.01 parts by weight or more, relative to 100 parts by weight of the acrylic polymer. In addition, from the perspective of being able to achieve a highly flexible adhesive layer, being able to fully relax the stress with the metal wiring, and thus preventing uneven display, the content (ratio) of the multifunctional (meth) acrylate is preferably 0.5 parts by weight or less, more preferably 0.4 parts by weight or less, and further preferably 0.3 parts by weight or less, relative to 100 parts by weight of the acrylic polymer.

[0201] [1-7. Silane coupling agent]

[0202] The acrylic adhesive composition of the present invention preferably further contains a silane coupling agent. When the adhesive composition contains a silane coupling agent, it is preferred because excellent adhesion to glass (especially excellent adhesion reliability to glass under high temperature and high humidity) can be easily obtained.

[0203] As the above-mentioned silane coupling agent, there is no particular limitation, and examples thereof include: γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-phenylaminopropyltrimethoxysilane, etc. Among them, γ-glycidoxypropyltrimethoxysilane is preferred. In addition, as the above-mentioned silane coupling agent, for example, commercial products such as the trade name "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) can also be cited. It should be noted that the silane coupling agent can be used alone or in combination of two or more.

[0204] The content of the silane coupling agent is not particularly limited, but is preferably 0.01 to 1 part by weight, more preferably 0.02 to 0.5 parts by weight, relative to 100 parts by weight of the acrylic polymer, from the viewpoint of improving the reliability of adhesion to glass.

[0205] [1-8. Cross-linking agent]

[0206] As described above, the acrylic pressure-sensitive adhesive composition of the present invention is preferably not a solvent-based composition, that is, preferably contains no crosslinking agent or substantially no crosslinking agent.

[0207] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, peroxide crosslinking agents, urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, Azoline crosslinking agents, aziridine crosslinking agents, amine crosslinking agents, etc. In particular, the acrylic adhesive composition of the present invention preferably does not contain or substantially does not contain an isocyanate crosslinking agent and / or an epoxy crosslinking agent as a crosslinking agent, and preferably does not contain or substantially does not contain an isocyanate crosslinking agent as a crosslinking agent.

[0208] In the acrylic adhesive composition of the present invention, "substantially free of" a crosslinking agent means that the crosslinking agent is not actively mixed except for the case where the crosslinking agent is inevitably mixed. Specifically, the case where the content of the crosslinking agent in the adhesive composition is 1.0 weight % or less (preferably 0.5 weight % or less, and more preferably 0.2 weight % or less) relative to the total amount of the adhesive composition (total weight, 100 weight %) can be referred to as substantially free of. In addition, the case where the content of the crosslinking agent is preferably 0.05 weight part or less (e.g., 0 to 0.05 weight part), more preferably 0.01 weight part or less (e.g., 0 to 0.01 weight part), and more preferably 0.001 weight part or less (e.g., 0 to 0.001 weight part) relative to the total amount of the monomer components constituting the acrylic polymer (100 weight parts), can be referred to as substantially free of.

[0209] [1-9. Additives]

[0210] The acrylic adhesive composition of the present invention may contain known additives such as a crosslinking accelerator, a tackifying resin (rosin derivatives, polyterpene resins, oil-soluble phenol resins, etc.), an anti-aging agent, a filler, a colorant (pigment, dye, etc.), an ultraviolet absorber, a chain transfer agent, a plasticizer, a softener, a surfactant, an antistatic agent, a rust inhibitor, and an antioxidant as needed within a range that does not impair the characteristics of the present invention. From the viewpoint of suppressing the increase in the haze of the adhesive layer of the present invention, the acrylic adhesive composition of the present invention preferably does not substantially contain a rust inhibitor or an antioxidant. It should be noted that such additives may be used alone or in combination of two or more.

[0211] From the viewpoint of suppressing the increase of the haze of the adhesive layer of the present invention, the acrylic adhesive composition of the present invention is preferably substantially free of antioxidants. "Substantially free of" antioxidants means that the antioxidants are not actively mixed except for the case where the antioxidants are inevitably mixed. Specifically, the case where the content of the antioxidant in the adhesive composition is 1.0 weight % or less (preferably 0.5 weight % or less, more preferably 0.2 weight % or less) relative to the total amount of the adhesive composition (total weight, 100 weight %) can be called substantially free. In addition, the content of the antioxidant is, for example, 0.5 weight part or less (for example, 0 weight part to 0.5 weight part), preferably 0.05 weight part or less (for example, 0 weight part to 0.05 weight part), more preferably 0.01 weight part or less (for example, 0 weight part to 0.01 weight part), and more preferably 0.001 weight part or less (for example, 0 weight part to 0.001 weight part) can be called substantially free.

[0212] [1-10. Preparation of acrylic adhesive composition]

[0213] The acrylic adhesive composition of the present invention can be prepared by mixing an acrylic polymer, a hydrogenated polyolefin resin as required, a multifunctional (meth) acrylate, a silane coupling agent, and other additives and uniformly stirring. At this time, from the viewpoint of adjusting the elastic modulus of the adhesive layer, the monomer components constituting the acrylic polymer can be matched. In the case of using the monomer components constituting the acrylic polymer in order to adjust the elastic modulus, in order to maintain the above-mentioned characteristics of the adhesive layer, it is preferred to prepare the acrylic polymer using a monomer mixture other than the monomer components used. As the monomer component for adjusting the elastic modulus, there is no particular restriction, for example, the above-mentioned functional group-containing monomer is preferred, and the above-mentioned hydroxyl-containing monomer is more preferred.

[0214] The amount of the monomer component for adjusting the elastic modulus used is not particularly limited. From the viewpoint of appropriately adjusting the elastic modulus of the adhesive layer, the amount of the monomer component for adjusting the elastic modulus used is preferably 5 to 30 parts by weight, and more preferably 10 to 20 parts by weight, relative to 100 parts by weight of all monomer units of the acrylic polymer (the total amount of monomer components constituting the acrylic polymer).

[0215] [2. Adhesive sheet]

[0216] The pressure-sensitive adhesive sheet of the present invention is not particularly limited in other respects as long as it has the pressure-sensitive adhesive layer of the present invention (particularly, a pressure-sensitive adhesive layer formed from the acrylic pressure-sensitive adhesive composition of the present invention).

[0217] The adhesive sheet of the present invention can be a double-sided adhesive sheet with both sides being the adhesive layer surface, or can be a single-sided adhesive sheet with only one side being the adhesive layer surface. Wherein, from the viewpoint of laminating two members to each other, it is preferably a double-sided adhesive sheet. It should be noted that in this specification, when referred to as "adhesive sheet", a tape-shaped adhesive sheet, i.e. "adhesive tape" is also included. In addition, in this specification, the adhesive layer surface is sometimes referred to as "adhesive face".

[0218] The pressure-sensitive adhesive sheet of the present invention may be provided with a release liner on the pressure-sensitive adhesive surface until use.

[0219] The adhesive sheet of the present invention may be a so-called "substrate-free" adhesive sheet (hereinafter sometimes referred to as a "substrate-free adhesive sheet") that does not have a substrate (substrate layer), or may be a type of adhesive sheet having a substrate (hereinafter sometimes referred to as a "substrate-free adhesive sheet"). As the above-mentioned substrate-free adhesive sheet, for example, a double-sided adhesive sheet consisting only of the above-mentioned adhesive layer, a double-sided adhesive sheet consisting of the above-mentioned adhesive layer and an adhesive layer other than the above-mentioned adhesive layer (sometimes referred to as "other adhesive layers"), etc. can be cited. On the other hand, as an adhesive sheet with a substrate, an adhesive sheet having the above-mentioned adhesive layer on at least one side of the substrate can be cited, etc. Among them, a substrate-free adhesive sheet (substrate-free double-sided adhesive sheet) is preferred, and a substrate-free double-sided adhesive sheet consisting only of the above-mentioned adhesive layer is more preferred. It should be noted that the above-mentioned "substrate (substrate layer)" does not include a release liner that is peeled off when the adhesive sheet is used (pasted).

[0220] Figure 1 1 is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the adhesive sheet of the present invention, wherein 1 represents an adhesive sheet, 10 represents an adhesive layer of the present invention, and 11 and 12 represent release liners. Figure 1 In the figure, the pressure-sensitive adhesive sheet 1 is a double-sided pressure-sensitive adhesive sheet without a substrate, and both pressure-sensitive adhesive surfaces of the pressure-sensitive adhesive layer 10 are protected by release liners 11 and 12 .

[0221] Since the adhesive layer 10 is composed of the adhesive layer of the present invention, the adhesive sheet 1 has high reliability that the adhesive strength does not change easily due to environmental changes, and the adhesive strength does not change much due to the storage environment immediately after film formation, and has excellent productivity.

[0222] The thickness (total thickness) of the adhesive sheet of the present invention is not particularly limited, preferably 12 μm to 350 μm, more preferably 12 μm to 300 μm. When the thickness is above a certain value, in a touch panel having an optical component (touch sensor film) having metal wiring such as a metal mesh film and a silver nanowire film, the stress with the metal wiring can be fully relaxed, thereby preventing uneven display, which is preferred. In addition, when the thickness is below a certain value, it is preferred to consider that it is easy to maintain an excellent appearance during manufacture and storage of the roll, and it is not easy to produce glue contamination during cutting. It should be noted that the thickness of the adhesive sheet of the present invention does not include the thickness of the release liner.

[0223] The adhesive sheet of the present invention is not particularly limited, and is preferably manufactured according to a known or customary manufacturing method. For example, in the case where the adhesive sheet of the present invention is a substrate-free adhesive sheet, the above-mentioned adhesive layer is formed on a release liner using the above-mentioned method. In addition, in the case where the adhesive sheet of the present invention is an adhesive sheet with a substrate, the above-mentioned adhesive layer can be obtained by directly forming the above-mentioned adhesive layer on the surface of the substrate (direct method), or the above-mentioned adhesive layer can be temporarily formed on the release liner, and then transferred (laminated) to the substrate, so as to obtain the above-mentioned adhesive layer on the substrate (transfer method).

[0224] The adhesive sheet of the present invention may have other layers in addition to the above-mentioned adhesive layer. As other layers, for example, other adhesive layers (adhesive layers other than the adhesive layer of the present invention), intermediate layers, primer layers, etc. It should be noted that the adhesive sheet of the present invention may have two or more other layers.

[0225] As the substrate in the case where the adhesive sheet of the present invention is an adhesive sheet with a substrate, there is no particular limitation, and examples thereof include: various optical films such as plastic films, anti-reflection (AR) films, polarizing plates, and phase difference plates. As materials for the above-mentioned plastic films, for example, polyester resins such as polyethylene terephthalate (PET), acrylic resins such as polymethyl methacrylate (PMMA), polycarbonates, triacetyl cellulose (TAC), polysulfones, polyarylates, polyimides, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, ethylene-propylene copolymers, plastic materials such as cyclic olefin polymers such as "ARTON (cyclic olefin polymer, manufactured by JSR Co., Ltd.)", and "ZEONOR (cyclic olefin polymer, manufactured by Japan Zeon Co., Ltd.)". It should be noted that these plastic materials can be used alone or in combination of two or more. In addition, the above-mentioned "substrate" refers to the part that is attached to the adherend together with the adhesive layer when the adhesive sheet is attached to the adherend. The release liner that is peeled off when the pressure-sensitive adhesive sheet is used (when attached) is not included in the “substrate”.

[0226] The substrate is preferably transparent. The total light transmittance of the substrate in the visible light wavelength range (based on JIS K7361-1) is not particularly limited, preferably 85% or more, more preferably 88% or more. In addition, the haze of the substrate (based on JIS K7136) is not particularly limited, preferably 1.0% or less, more preferably 0.8% or less. As such a transparent substrate, for example, PET film, trade name "ARTON", trade name "ZEONOR" and other non-oriented films can be cited.

[0227] The thickness of the substrate is not particularly limited, and is preferably 12 μm to 500 μm, for example. It should be noted that the substrate may have any form of a single layer or a multilayer. In addition, the surface of the substrate may be appropriately subjected to a known and commonly used surface treatment such as a physical treatment such as a corona discharge treatment or a plasma treatment, or a chemical treatment such as a primer treatment.

[0228] Adhesive sheet of the present invention can be provided with release liner on adhesive face until before use.In addition, when adhesive sheet of the present invention is double-sided adhesive sheet, each adhesive face can be protected by 2 release liners respectively, and can also be protected by the release liner of 1 two sides as the release face with the form of winding into roll.Release liner is used as the protective material of adhesive layer, is peeled off when being pasted on adherend.In addition, when adhesive sheet of the present invention is substrate-free adhesive sheet, release liner also plays the effect of the support as adhesive layer.It should be noted that release liner can be unnecessary to be provided.

[0229] The adhesive sheet of the present invention has an adhesive layer of the present invention (particularly an adhesive layer formed by the acrylic adhesive composition of the present invention), so the reliability of the adhesive force not easily changing with respect to environmental changes is high, the change of the adhesive force caused by the storage environment just after the film is formed is small, and the productivity is excellent. In addition, the flexibility is excellent, and even when an optical component (touch sensor film) with metal wiring such as a metal mesh film and a silver nanowire film is attached, the display unevenness of the display device and the input device can be prevented. In addition, the adhesiveness, foaming peeling resistance, and height difference tracking are excellent.

[0230] Therefore, the adhesive sheet of the present invention can be used in an image display device, in a touch panel in which a touch sensor is assembled in these image display devices, to paste optical components such as a polarizing film, a phase difference film, an optical compensation film, a touch sensor film, a cover film on the image display panel, or to paste these optical components to each other. In addition, the adhesive sheet of the present invention can also be used for an adherend that is prone to foaming at the interface at high temperatures. For example, polymethyl methacrylate resin (PMMA) sometimes contains unreacted monomers, and foaming caused by foreign matter is easily generated at high temperatures. In addition, polycarbonate (PC) is prone to outgassing of water and carbon dioxide at high temperatures. The adhesive sheet of the present invention has excellent resistance to foaming and peeling, so it can be used for plastic adherends containing such resins.

[0231] In addition, the adhesive sheet of the present invention can be used for adherends with a large linear expansion coefficient in addition to adherends with a small linear expansion coefficient. It should be noted that the adherends with a small linear expansion coefficient are not particularly limited, and examples thereof include glass plates (linear expansion coefficient: 0.3×10 -5 / ℃~0.8×10 -5 / ℃), polyethylene terephthalate substrate (PET film, linear expansion coefficient: 1.5×10 -5 / ℃~2×10 -5 / °C). In addition, there are no particular restrictions on the adherend having a large linear expansion coefficient, and examples thereof include: a resin substrate having a large linear expansion coefficient, and more specifically, a polycarbonate resin substrate (PC, linear expansion coefficient: 7×10 -5 / ℃~8×10 -5 / ℃)、PMMA、Linear expansion coefficient:7×10 -5 / ℃~8×10 -5 / ℃), cycloolefin polymer substrate (COP, linear expansion coefficient: 6×10 -5 / ℃~7×10 -5 / °C), trade name “ZEONOR” (manufactured by Zeon Co., Ltd.), trade name “ARTON” (manufactured by JSR Corporation), etc.

[0232] The adhesive sheet of the present invention can be used for bonding an adherend with a small linear expansion coefficient to an adherend with a large linear expansion coefficient. Specifically, the adhesive sheet of the present invention is preferably used for bonding a glass adherend (e.g., a glass plate, chemically strengthened glass, a glass lens, etc.) to the above-mentioned resin substrate with a large linear expansion coefficient.

[0233] As described above, the pressure-sensitive adhesive sheet of the present invention can be used for bonding adherends made of various materials to each other, and can be used particularly for bonding a glass adherend to a plastic adherend.

[0234] In addition, the adhesive sheet of the present invention can be used for adherends with smooth surfaces, and can also be used for adherends with height differences on the surface, such as optical components (touch sensor films) having metal wiring such as metal mesh films and silver nanowire films. In particular, even if at least one of a glass adherend and the above-mentioned resin substrate with a large linear expansion coefficient has a height difference on the surface, the adhesive sheet of the present invention can be used for bonding a glass adherend to the above-mentioned resin substrate with a large linear expansion coefficient.

[0235] The adhesive sheet of the present invention is preferably used for the manufacture of portable electronic devices. Examples of the portable electronic devices include: mobile phones, PHS, smart phones, tablet computers (tablet computers), mobile computers (mobile PCs), portable information terminals (PDAs), electronic notepads, portable televisions, portable radios and other portable broadcast receivers, portable game consoles, portable audio players, portable DVD players, cameras such as digital cameras, and portable video cameras.

[0236] The adhesive sheet of the present invention is preferably used, for example, for the bonding of components and modules constituting portable electronic devices, the fixing of components and modules constituting portable electronic devices to the housing, etc. More specifically, it can be cited as follows: the bonding of protective glass, lens (especially glass lens) and touch panel, touch sensor film (especially touch sensor film with metal wiring such as metal mesh film and silver nanowire film); the bonding of polarizing film and touch panel and touch sensor; the bonding of display panel and touch panel and touch sensor film; the fixing of protective glass and lens (especially glass lens) to the housing; the fixing of display panel to the housing; the fixing of input devices such as sheet keyboard and touch panel to the housing; the bonding of protective panel of information display part to the housing; the bonding of housings to each other; the bonding of housing and decorative sheet; the fixing and bonding of various components and modules constituting portable electronic devices, etc. It should be noted that in this specification, the display panel refers to a structure consisting of at least a lens (especially a glass lens) and a touch panel. In addition, the lens in this specification is a concept that includes both a transparent body that shows the refraction of light and a transparent body that does not have the refraction of light. That is, the lens in this specification also includes a simple window panel that does not have a refractive effect.

[0237] In addition, the adhesive sheet of the present invention is preferably used for optical purposes. That is, the adhesive sheet of the present invention is preferably an optical adhesive sheet for optical purposes. More specifically, for example, it is preferably used for purposes of laminating optical components (optical component lamination), manufacturing purposes of products (optical products) using the above optical components, etc.

[0238] [3. Optical member with adhesive layer, image display device, touch panel]

[0239] The optical component with adhesive layer of the present invention is an optical component with adhesive layer having adhesive sheet of the present invention pasted on at least one side of the optical component, and is not particularly limited in other aspects. It should be noted that the adhesive layer of the optical component with adhesive layer of the present invention may be provided with a release liner on the adhesive surface until use, or may not be provided with a release liner. The optical component with adhesive layer of the present invention is formed by pasting the adhesive sheet of the present invention, so the reliability that the adhesive force is not easy to change with respect to environmental changes is high, the change of adhesive force caused by the storage environment just after film formation is small, and the productivity is excellent. In addition, it has high flexibility, can fully relax the stress with the metal wiring, thereby preventing uneven display, and has excellent adhesion reliability, especially adhesion reliability at high temperature.

[0240] The optical component with an adhesive layer of the present invention may be an optical component with an adhesive layer having an optical component (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film, and the adhesive sheet of the present invention is attached to the optical component. In this case, the adhesive sheet of the present invention is preferably attached to the surface of the touch sensor film on the side having the above-mentioned metal wiring.

[0241] Figure 2 Schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the optical member with a pressure-sensitive adhesive layer of the present invention. Figure 2 In (a), 2A represents an optical member with an adhesive layer, 20 represents the adhesive layer of the present invention, 21 represents an optical member, and 22 represents a release liner. The adhesive layer 20 is laminated on one side of the optical member 21, and the adhesive surface of the adhesive layer 20 on the opposite side to the optical member 21 is protected by the release liner 22. Figure 2In (b), 2B represents an optical member with an adhesive layer (touch sensor film with an adhesive layer), 20 represents an adhesive layer of the present invention, 23 represents a touch sensor film, 22 represents a release liner, and 24 represents a metal wiring. The adhesive layer 20 is laminated on the surface of the touch sensor film 23 on which the metal wiring 24 is formed, and the adhesive surface of the adhesive layer 20 on the opposite side to the touch sensor film 23 is protected by the release liner 22. The adhesive layer 20 is composed of the adhesive layer of the present invention, so the optical member 2A with an adhesive layer and the touch sensor film 2B with an adhesive layer have high reliability that the adhesive force does not change easily with respect to environmental changes, the change in adhesive force caused by the storage environment immediately after film formation is small, and the productivity is excellent.

[0242] From the viewpoint of obtaining a better anticorrosion effect, the pressure-sensitive adhesive layer-attached optical member preferably has a pressure-sensitive adhesive layer attached to the surface of the optical member opposite to the side having the pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer is preferably the pressure-sensitive adhesive layer of the present invention.

[0243] Optical components refer to components with optical properties (such as polarization, light refraction, light scattering, light reflection, light transmittance, light absorption, light diffraction, optical rotation, visual recognition, etc.). As substrates constituting the above-mentioned optical components, there are no particular restrictions, for example, substrates constituting devices (optical devices) such as image display devices and touch panels or substrates used in these devices, such as polarizing films, wavelength plates, phase difference films, optical compensation films, brightness enhancement films, light guide plates, reflective films, anti-reflective films, hard coating films (films hard-coated on at least one side of plastic films such as PET films), transparent conductive films (for example, plastic films having an ITO layer on the surface (preferably PET-ITO, polycarbonate-ITO, cycloolefin polymer-ITO, etc. ITO films)), design films, decorative films, surface protection plates, prisms, lenses, color filters, transparent substrates (glass sensors, glass display panels (LCDs, etc.), glass substrates such as glass plates with transparent electrodes, etc.), and substrates stacked therefrom (sometimes collectively referred to as "functional films"), etc. In addition, these films may also have metal wiring such as a metal nanowire layer and a conductive polymer layer. In addition, metal fine wires may be screen-printed on these films. It should be noted that the above-mentioned "plate" and "film" each include a plate-like, film-like, sheet-like form, etc. For example, a "polarizing film" includes a "polarizing plate" and a "polarizer", etc. In addition, a "film" includes a film sensor, etc.

[0244] In particular, the adhesive sheet of the present invention can be suitable for transparent conductive films (metal mesh films, silver nanowire films) in which the above-mentioned metal wiring is metal mesh wiring or silver nanowires, and in particular optical components (touch sensor films) having metal mesh films. When optical components having metal wiring such as metal mesh films and silver nanowire films are bonded by adhesive sheets, there is a problem of uneven display at the periphery of the image display panel due to stress and strain of the adhesive applied to the periphery of the metal wiring. Therefore, for the adhesive layer of the adhesive sheet bonded to the optical component having metal wiring, in order to prevent uneven display, flexibility is required to relax the stress of the metal wiring.

[0245] In the adhesive sheet of the present invention, the adhesive layer of the present invention has high flexibility, and even when a film having metal wiring such as a metal mesh film or a silver nanowire film is attached, the stress on the metal wiring can be fully relaxed, thereby preventing uneven display. In addition, in an image display device or a touch panel having the adhesive sheet of the present invention, optical components are attached using a highly reliable adhesive layer whose adhesive strength is not easily changed with environmental changes, so the durability is excellent.

[0246] Examples of the image display device include a liquid crystal display device, an organic EL (electroluminescence) display device, a PDP (plasma display panel), and electronic paper.

[0247] There are no particular restrictions on the substrate constituting the optical component, and examples thereof include substrates (e.g., sheet-shaped, film-shaped, plate-shaped substrates, etc.) comprising glass, acrylic resin, polycarbonate, polyethylene terephthalate, cycloolefin polymer, metal thin film, etc. It should be noted that, as described above, the "optical component" in the present invention also includes components (design films, decorative films, surface protection films, etc.) that play a decorative and protective role while maintaining the visual recognizability of the image display device and the touch panel.

[0248] If the pressure-sensitive adhesive sheet of the present invention is a pressure-sensitive adhesive sheet with a substrate and the pressure-sensitive adhesive sheet constitutes a member having optical properties, the substrate can be regarded as the same as the substrate, and the pressure-sensitive adhesive sheet can also be regarded as an optical member with a pressure-sensitive adhesive layer of the present invention.

[0249] When the PSA sheet of the present invention is a PSA sheet with a substrate and the functional film is used as the substrate, the PSA sheet of the present invention can be used as an "adhesive functional film" having the PSA layer on at least one side of the functional film.

[0250] Figure 3 It is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the image display device of the present invention.

[0251] exist Figure 3In the figure, 3 represents an image display device, 30, 31, and 32 represent adhesive layers, 33 represents an image display panel, 34 and 35 represent polarizing films, and 36 represents a transparent substrate. The image display device 3 is stacked with a polarizing film 35, an adhesive layer 32, an image display panel 33, an adhesive layer 31, a polarizing film 34, an adhesive layer 30, and a transparent substrate 36 in this order.

[0252] At least one of the adhesive layers 30, 31, and 32 is composed of the adhesive layer of the present invention. The image display device 3 includes the adhesive layer of the present invention in a laminated structure, and thus has high reliability that the adhesive force is not easily changed by environmental changes, and has excellent durability.

[0253] In the image display device 3, the adhesive layer 30 is located at the position closest to the visible side of the stacked structure and is most susceptible to the external environment such as the temperature, humidity, and external light of the external air. Therefore, the adhesive layer 30 is preferably composed of the adhesive layer of the present invention, which has high reliability and excellent durability and whose adhesive strength is not easily changed with environmental changes.

[0254] It is preferred that both or one of the adhesive layers 31 and 32 be composed of the adhesive layer of the present invention, but it is not necessary for them to be composed of the adhesive layer of the present invention.

[0255] The touch panel of the present invention is an image display device in which an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film is incorporated.

[0256] Figure 4 It is a schematic diagram (cross-sectional view) showing a specific example of a preferred embodiment of the touch panel of the present invention.

[0257] exist Figure 4 4 denotes a touch panel, 40, 41, and 42 denote adhesive layers, 43 denotes an image display panel, 44 denotes a touch sensor film, 45 denotes a polarizing film, 46 denotes a transparent substrate, and 47 denotes a metal wiring. The metal wiring 47 is wired on one surface of the touch sensor film 44. The touch panel 4 is sequentially stacked with a polarizing film 45, an adhesive layer 42, an image display panel 43, an adhesive layer 41, a touch sensor film 44, an adhesive layer 40, and a transparent substrate 46, and the adhesive layer 40 is stacked on the surface of the touch sensor film 44 on which the metal wiring 47 is arranged.

[0258] At least one of the adhesive layers 40, 41, and 42 is composed of the adhesive layer of the present invention. The touch panel 4 includes the adhesive layer of the present invention in a laminated structure, and thus has high reliability that the adhesive force is not easily changed by environmental changes, and has excellent durability.

[0259] In the touch panel 4, the adhesive layer 40 is located at the position closest to the visible side of the stacked structure and is most susceptible to the external environment such as the temperature, humidity, and external light of the external air. In addition, the adhesive layer 40 is stacked on the surface of the touch sensor film 44 on which the metal wiring 47 is arranged, so that it fully follows the height difference formed by the metal wiring 47 without residual bubbles. Therefore, the adhesive layer 40 is preferably composed of an adhesive layer of the present invention with high reliability and excellent durability, in which the adhesive force is not easily changed with respect to environmental changes. In addition, the adhesive layer 40 is preferably composed of an adhesive layer of the present invention with excellent height difference tracking. Preferably, both or one of the adhesive layers 41 and 42 are composed of the adhesive layer of the present invention, but it may not be composed of the adhesive layer of the present invention.

[0260] The method for forming the metal wiring on the touch sensor film is not particularly limited, and examples thereof include a method of removing a preliminarily provided metal layer by etching or the like, and a printing method.

[0261] The image display device and touch panel of the present invention may further have optical components such as a wavelength plate, a phase difference film, and an optical compensation film. These optical components may be single or multiple. There is no particular limitation on the bonding method of these optical components, and examples thereof include: (1) bonding the adhesive sheet of the present invention to the optical component with the adhesive layer of the present invention; (2) bonding the adhesive sheet other than the adhesive sheet of the present invention to the optical component with the adhesive layer of the present invention, etc.

[0262] Example

[0263] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to these Examples. It should be noted that all blending parts (parts by weight) represent the blending parts of each component described.

[0264] [Manufacturing Example 1: Preparation of Prepolymer Composition A]

[0265] A monomer mixture consisting of 56 parts by weight of 2-ethylhexyl acrylate (2EHA), 24 parts by weight of isostearyl acrylate (ISTA), 19 parts by weight of N-vinyl-2-pyrrolidone (NVP) and 1 part by weight of 4-hydroxybutyl acrylate (4-HBA) was added with 0.03 parts by weight of a photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.03 parts by weight of a photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV), and then irradiated with ultraviolet rays until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) reached about 20 Pa·s, thereby obtaining a prepolymer composition A in which part of the above-mentioned monomer components were polymerized.

[0266] [Manufacturing Example 2: Preparation of Prepolymer Composition B]

[0267] A monomer mixture consisting of 56 parts by weight of 2-ethylhexyl acrylate (2EHA), 24 parts by weight of isostearyl acrylate (ISTA), 14 parts by weight of N-vinyl-2-pyrrolidone (NVP) and 6 parts by weight of 4-hydroxybutyl acrylate (4-HBA) was added with 0.03 parts by weight of a photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.03 parts by weight of a photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV), and then irradiated with ultraviolet rays until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) reached about 20 Pa·s, thereby obtaining a prepolymer composition B in which part of the above-mentioned monomer components were polymerized.

[0268] [Production Example 3: Preparation of Prepolymer Composition C]

[0269] 0.05 parts by weight of a photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.05 parts by weight of a photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV) were added to a monomer mixture consisting of 40.5 parts by weight of 2-ethylhexyl acrylate (2EHA), 40.5 parts by weight of isostearyl acrylate (ISTA), 18 parts by weight of N-vinyl-2-pyrrolidone (NVP) and 1 part by weight of 4-hydroxybutyl acrylate (4-HBA), and then irradiated with ultraviolet rays until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measuring temperature 30°C) reached about 20 Pa·s, thereby obtaining a prepolymer composition C in which part of the above-mentioned monomer components were polymerized.

[0270] [Production Example 4: Preparation of Prepolymer Composition D]

[0271] A monomer mixture consisting of 67 parts by weight of butyl acrylate (BA), 14 parts by weight of cyclohexyl acrylate (CHA) and 19 parts by weight of 4-hydroxybutyl acrylate (4-HBA) was mixed with 0.09 parts by weight of a photopolymerization initiator (trade name "Omnirad 184", manufactured by IGM Resins BV) and 0.09 parts by weight of a photopolymerization initiator (trade name "Omnirad 651", manufactured by IGM Resins BV), and then irradiated with ultraviolet rays until the viscosity (BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached about 20 Pa·s, thereby obtaining a prepolymer composition D in which part of the above-mentioned monomer components was polymerized.

[0272] [Example 1]

[0273] To 100 parts by weight of the prepolymer composition A obtained in Production Example 1 were added 1.5 parts by weight of hydrogenated 1,2-polybutadiene (trade name "BI-3000", number average molecular weight (Mn): 4750 (measured value), weight average molecular weight (Mw): 6150 (measured value), polydispersity (Mw / Mn): 1.30 (measured value), hydrogenation rate: 97% or more (product catalog value), iodine value: 21 or less (product catalog value), manufactured by Nippon Soda Co., Ltd.), and 1.5 parts by weight of hydrogenated 1,2-polybutadiene diol (trade name "GI-2000", number average molecular weight (Mw): 6150 (measured value), polydispersity (Mw / Mn): 1.30 (measured value), hydrogenation rate: 97% or more (product catalog value), iodine value: 21 or less (product catalog value), manufactured by Nippon Soda Co., Ltd.). n): 3110 (measured value), weight average molecular weight (Mw): 5090 (measured value), polydispersity (Mw / Mn): 1.64 (measured value), hydrogenation rate: 93% or more (product catalog value), iodine value: 21 or less (product catalog value), 21 parts by weight of an alkylene glycol (manufactured by Nippon Soda Co., Ltd.), 0.07 parts by weight of trimethylolpropane triacrylate (TMPTA), and 0.3 parts by weight of a silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.), and mixed to obtain an adhesive composition (pre-curing composition).

[0274] The above-mentioned adhesive composition is coated on a polyethylene terephthalate (PET) release liner (heavy release liner, trade name "MRF75", manufactured by Mitsubishi Resins Corporation) in a final thickness (thickness of the adhesive layer) of 250 μm, thereby forming a coating layer (adhesive composition layer). Next, a PET release liner (light release liner, trade name "MRE75", manufactured by Mitsubishi Resins Corporation) is set on the above-mentioned coating layer to cover the coating layer and block oxygen. Then, a laminate of MRF75 / coating layer (adhesive composition layer) / MRE75 is obtained. Next, a black light lamp (manufactured by Toshiba Corporation) is used to irradiate the laminate from the upper surface (MRF38 side) of the laminate with an illumination of 5 mW / cm 2 The film was irradiated with ultraviolet light for 300 seconds. Then, it was dried in a 90°C dryer for 2 minutes to volatilize the residual monomer. Then, a substrate-free double-sided adhesive sheet consisting only of an adhesive layer and having both sides of the adhesive layer protected by release liners was obtained.

[0275] [Example 2 to Example 3, Comparative Example 1]

[0276] A substrate-less double-sided PSA sheet was obtained in the same manner as in Example 1 except that the composition of the PSA composition and the thickness of the PSA layer were adjusted to those shown in Table 1.

[0277] [Table 1]

[0278]

[0279] The details of the components shown in Table 1 are as follows.

[0280] (Prepolymer composition)

[0281] A: Prepolymer composition A prepared in Preparation Example 1

[0282] B: Prepolymer composition B produced in Production Example 2

[0283] C: Prepolymer composition C produced in Production Example 3

[0284] D: Prepolymer composition D prepared in Preparation Example 4

[0285] (monomer)

[0286] HEA: 2-Hydroxyethyl Acrylate

[0287] 4-HBA: 4-Hydroxybutyl acrylate

[0288] (Hydrogenated Polyolefin)

[0289] BI-3000: Trade name "BI-3000", hydrogenated 1,2-polybutadiene, number average molecular weight (Mn): 4750 (measured value), weight average molecular weight (Mw): 6150 (measured value), polydispersity (Mw / Mn): 1.30 (measured value), hydrogenation rate: 97% or more (product catalog value), iodine value: 21 or less (product catalog value), manufactured by Nippon Soda Co., Ltd.

[0290] GI-2000: Trade name "GI-2000", hydrogenated 1,2-polybutadiene diol, number average molecular weight (Mn): 3110 (measured value), weight average molecular weight (Mw): 5090 (measured value), polydispersity (Mw / Mn): 1.64 (measured value), hydrogenation rate: 97% or more (product catalog value), iodine value: 21 or less (product catalog value), manufactured by Nippon Soda Co., Ltd.

[0291] (Multifunctional acrylate)

[0292] TMPTA: Trimethylolpropane triacrylate

[0293] DPHA: Dipentaerythritol hexaacrylate

[0294] (Silane coupling agent)

[0295] KBM-403: Trade name "KBM-403", 3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.

[0296] The measured values ​​of the number average molecular weight (Mn), weight average molecular weight (Mw) and polydispersity (Mw / Mn) of the hydrogenated polyolefin are obtained from values ​​calculated by polystyrene conversion by GPC (gel permeation chromatography) under the following conditions.

[0297] Analytical device: GPC: HLC-8320GPC (Tosoh)

[0298] Determination conditions:

[0299] Column: TSKgel SuperHZM-H / HZ4000 / HZ3000 / HZ2000

[0300] Column size: 6.0mm inner diameter x 150mm

[0301] Eluent: THF (tetrahydrofuran)

[0302] Flow rate: 0.6mL / min

[0303] Detector: Differential Refractometer (RI)

[0304] Column temperature: 40°C

[0305] Injection volume: 20 μL

[0306] The molecular weight was calculated based on polystyrene conversion.

[0307] [Characteristics evaluation]

[0308] The substrate-free double-sided PSA sheets of Examples and Comparative Examples were subjected to the following measurements or evaluations.

[0309] (1) Determination method of water absorption rate and water absorption rate

[0310] The substrate-free double-sided adhesive sheets of the examples and comparative examples were cut into 1 cm squares, and the adhesive layer with the release liners on both sides peeled off was placed in a moisture adsorption and desorption measuring device (IGA-sorp, manufactured by Hiden Co., Ltd.) to perform moisture adsorption and desorption measurement. The measurement mode was set to the sequential mode, and the weight was measured over time when the environmental conditions were changed according to the program sequence shown in Table 2 below.

[0311] [Table 2]

[0312] Program Order Temperature setting (℃) Humidity setting (%RH) Standing time (minutes) 1 150 0 60 2 23 0 240 3 23 25 240 4 23 50 240 5 23 75 360 6 23 90 360 7 23 75 360 8 23 50 360 9 23 25 240 10 23 0 240

[0313] The time when process 2 ends is regarded as an absolute dry state, and the weight change rate at the end of process 2 to process 6 obtained from the absolute dry state by the following formula is regarded as water absorption rate X0, X25, X50, X75, X90 (%), respectively.

[0314] Water absorption rate (%) = (weight at the end of each program - weight at the end of program 2 (absolutely dry state)) / (weight at the end of program 2 (absolutely dry state)) × 100

[0315] In addition, the time (minutes) from the water absorption at the start of the above-mentioned procedures 3 to 6 (the water absorption at the end of the previous procedure) to the water absorption at the end of each procedure reaching half the value was measured and designated as water absorption rates T25, T50, T75, and T95, respectively. The results are shown in Table 3.

[0316] (2) Method for measuring adhesive strength

[0317] The light release liner is peeled off from the substrate-free double-sided adhesive sheet of the embodiment and the comparative example, and a PET film (Lumirror S10, manufactured by Toray Industries, Ltd., with a thickness of 25 μm) is laminated on the exposed surface of the exposed adhesive layer to obtain a laminate. Then, a test piece (width 20 mm × length 150 mm) is cut out from the laminate, the heavy release liner is peeled off, and the glass plate (Qingban Green Grinding Products, manufactured by Matsunami Glass Co., Ltd.) is laminated. In this lamination, the test piece is crimped to the adherend by making a 2kg roller go back and forth once under an environment of 25°C. From the above lamination, stand at 23°C for 2 minutes, then implement a peel test of peeling the test piece from the glass plate, and measure the peel strength as the adhesive force. In the above measurement, the measurement temperature is set to 23°C, the peeling angle of the test piece relative to the adherend is set to 180°, the pulling speed of the test piece is set to 300mm / minute, and the peeling length is set to 50mm (measurement conditions of the peeling test). After the adhesive layer was formed into a film, the adhesive strength was measured by the above method within 12 hours, and the initial adhesive strength (N / 20mm) was set as Y0. Then, for the test pieces stored at 23°C and 50% RH for 24 hours, 48 ​​hours, 120 hours, 144 hours, 168 hours, and 216 hours, the adhesive strength (N / 20mm) was measured by the above method, and the values ​​were set as Y24, Y48, Y120, Y144, Y168, and Y216, respectively. The graphs showing the changes in the adhesive strength are shown in FIG. Figure 5 The initial adhesive force Y0, the adhesive force Y48 after storage for 48 hours, and the rate of change of the adhesive force from Y0 to Y48 ((Y0-Y48) / Y0×100)(%) are shown in Table 3. It can be seen that in Comparative Example 1 where X90 is greater than 1.5%, a sharp decrease in adhesive force is observed 48 hours after the initial adhesive force, while in Examples 1 to 3 where X90 is 1.5% or less, the variation of adhesive force from the initial adhesive force is small, showing highly reliable adhesive force.

[0318] [Table 3]

[0319]

[0320] Modifications of the present invention will be described below.

[0321] [Note 1]

[0322] A pressure-sensitive adhesive composition for forming a pressure-sensitive adhesive layer used for bonding optical members of an image display device, wherein the pressure-sensitive adhesive layer satisfies the following formula (1) when the water absorption rate when stored under conditions of 23° C. and 90% RH for 360 minutes is X90 (%).

[0323] X90≤1.5% …… (1)

[0324] [Note 2]

[0325] The adhesive composition according to Supplementary Note 1, wherein the following formula (2) is satisfied when the water absorption rate of the adhesive layer when stored under conditions of 23° C. and 25% RH for 240 minutes is defined as X25 (%).

[0326] X90-X25≤1.5%……(2)

[0327] [Note 3]

[0328] The adhesive composition according to Supplementary Note 1 or 2, wherein the following formula (3) is satisfied when the time until the water absorption reaches a half value of the water absorption between X75 (%) and X90 (%) is T90 (minutes).

[0329] T90≥16 minutes……(3)

[0330] The X75 is the water absorption rate when the adhesive layer is stored at 23° C. and 75% RH for 360 minutes, and the X90 is the water absorption rate when the adhesive layer is stored at 23° C. and 90% RH for 360 minutes.

[0331] [Note 4]

[0332] The adhesive composition according to Supplementary Note 3, wherein when the time until the water absorption reaches a half value of the water absorption between an absolutely dry state and X25 (%) is defined as T25 (minutes), the following formula (4) is satisfied.

[0333] T90 / T25≥1.0 …… (4)

[0334] The X25 is the water absorption rate when the pressure-sensitive adhesive layer is stored under the conditions of 23° C. and 25% RH for 240 minutes.

[0335] [Note 5]

[0336] A pressure-sensitive adhesive layer, comprising the pressure-sensitive adhesive composition according to any one of Appendixes 1 to 4.

[0337] [Note 6]

[0338] A pressure-sensitive adhesive sheet comprising the pressure-sensitive adhesive layer according to Supplementary Note 5.

[0339] [Note 7]

[0340] An optical member with a pressure-sensitive adhesive layer, wherein the pressure-sensitive adhesive sheet according to Supplementary Note 6 is adhered to at least one surface of the optical member.

[0341] [Note 8]

[0342] An image display device comprising the pressure-sensitive adhesive layer-attached optical member according to Supplementary Note 7.

[0343] [Note 9]

[0344] The image display device according to Supplementary Note 8, wherein the image display device is a touch panel.

Claims

1. An adhesive composition for forming an adhesive layer used for bonding an optical member of an image display device, wherein: When the water absorption rate of the adhesive layer when stored under the conditions of 23° C. and 90% RH for 360 minutes is defined as X90 (%), the following formula (1) is satisfied: X90≤1.5% …… (1)。 2. The adhesive composition according to claim 1, wherein When the water absorption rate of the adhesive layer when stored at 23° C. and 25% RH for 240 minutes is defined as X25 (%), the following formula (2) is satisfied: X90-X25≤1.5%......(2).

3. The adhesive composition according to claim 1, wherein When the time until the water absorption reaches the half value of the water absorption between X75 (%) and X90 (%) is defined as T90 (minutes), the following formula (3) is satisfied: T90≥16 minutes……(3) The X75 is the water absorption rate when the adhesive layer is stored at 23° C. and 75% RH for 360 minutes, and the X90 is the water absorption rate when the adhesive layer is stored at 23° C. and 90% RH for 360 minutes.

4. The adhesive composition according to claim 2, wherein When the time until the water absorption reaches the half value of the water absorption between X75 (%) and X90 (%) is defined as T90 (minutes), the following formula (3) is satisfied: T90≥16 minutes……(3) The X75 is the water absorption rate when the adhesive layer is stored at 23° C. and 75% RH for 360 minutes, and the X90 is the water absorption rate when the adhesive layer is stored at 23° C. and 90% RH for 360 minutes.

5. The adhesive composition according to claim 3, wherein When the time until the water absorption reaches the half value of the water absorption between the absolute dry state and X25 (%) is set to T25 (minutes), the following formula (4) is satisfied: T90 / T25≥1.0 …… (4) The X25 is the water absorption rate when the pressure-sensitive adhesive layer is stored under the conditions of 23° C. and 25% RH for 240 minutes.

6. The adhesive composition according to claim 4, wherein When the time until the water absorption reaches the half value of the water absorption between the absolute dry state and X25 (%) is set to T25 (minutes), the following formula (4) is satisfied: T90 / T25≥1.0 …… (4) The X25 is the water absorption rate when the pressure-sensitive adhesive layer is stored under the conditions of 23° C. and 25% RH for 240 minutes.

7. An adhesive layer, wherein: The adhesive layer is formed from the adhesive composition according to any one of claims 1 to 6.

8. An adhesive sheet, wherein: The pressure-sensitive adhesive sheet comprises the pressure-sensitive adhesive layer according to claim 7 .

9. An optical member with an adhesive layer, wherein: The pressure-sensitive adhesive sheet according to claim 8 is bonded to at least one surface of the optical member.

10. An image display device, wherein: The image display device comprises the pressure-sensitive adhesive layer-attached optical member according to claim 9.

11. The image display device according to claim 10, wherein: The image display device is a touch panel.